Parallel volcanic chains generated by plume-slab interaction - Ben R. Mather; Maria Seton; Simon Williams; Joanne M. Whittaker; Rebecca Carey; Maëlis Arnould; Nicolas Coltice; Angus Rogers; Saskia Ruttor; Oliver Nebel; Christopher Gonzalez (Gondwana Research, 2026)

Enhancements to the USGS Landsat Level 2 surface temperature and emissivity product for Collection 3 reprocessing - Saeed Arab; Chase Mueller; Christopher J. Crawford; Danika Wellington; Ray Dittmeier; Glynn Hulley; Aaron Gerace; Calli Jenkerson; Simon Hook; Amirhossein Hassanzadeh; Rehman Eon; Cody Anderson; et al. (Remote Sensing of Environment, 2026)

Neanderthals in the desert? Population history best explains Middle Palaeolithic technological heterogeneity in Arabia - James Blinkhorn; Huw S. Groucutt; W. Christopher Carleton; Eric Andrieux; Simon J. Armitage; Ceri Shipton; Paul S. Breeze; Nick Drake; Abdulaziz Al-Omari; Faisal Al-Jibreen; Abdullah M. Alsharekh; Eleanor M.L. Scerri; et al. (Quaternary Science Reviews, 2026)

Biomonitoring Equivalents for interpreting mandelic and phenylglyoxylic acid in urine resulting from exposures to styrene and ethylbenzene - Sean M. Hays; Ted W. Simon; Xichen Chou; Christopher R. Kirman (Regulatory Toxicology and Pharmacology, 2026)

The Effectiveness of the Advanced Cooking Education 4-H After-School Club Intervention on Diet Behaviors of Students at Title I New York City Middle Schools - Lauren San Diego; Caitlin Potter; Stephen Parry; Christopher Loss; Jamila Simon; Tashara M. Leak (Journal of Nutrition Education and Behavior, 2026)

Ohmic heating inactivation of Clostridium sporogenes in green bean puree and its effect on sensory attributes - Shyam Kumar Singh; Ömer Faruk Çokgezme; Ran Tao; Ashley M. Soldavini; Christopher Simons; Sudhir K. Sastry (Journal of Food Engineering, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Extracellular electron transfer by the cultured coral photosymbiont Symbiodinium microadriaticum - Loris Marcel; James T. Simon; Joshua M. Lawrence; Svetlana Menkin; Adrian C. Barbrook; R. Ellen R. Nisbet; Christopher J. Howe; Jenny Z. Zhang (Photosynthesis Research, 2026)
Photosynthetic microorganisms may show extracellular electron transfer (EET), in which some of the electrons generated by photosynthesis or respiration are lost from the cell. Most studies have focussed on cyanobacteria, with very few on eukaryotic algae. Here we demonstrate EET from the eukaryotic dinoflagellate alga Symbiodinium microadriaticum , a species that can form symbiosis with corals and other Cnidaria. We show that the EET involves diffusible electroactive species, which may represent a previously unsuspected route for communication between symbionts and hosts. We show that EET can be used to study photosynthetic and respiratory functions in the dinoflagellate. We also show that it can provide information on the effects of environmental stresses including changes in temperature (linked to coral bleaching), pH and light intensity. The electrochemical platform outlined in this study offers a novel tool for studying dinoflagellate physiology, the coral-dinoflagellate symbiosis, and the molecular mechanisms of bleaching.

Assessment of two minimally invasive methodologies for sex identification in the European eel, Anguilla anguilla - Michael J. Williamson; Jack A. Brand; Kevin Hopkins; Luke O'Connor; Matthew W. Perkins; Christopher Sergeant; Simon Spiro; Taina Strike; Jessica Whinfield; Rosie S. Williams; Ethan Wrigglesworth; Rosalind M. Wright; et al. (Journal of Fish Biology, 2026)
Sex is an important driver of variation in behaviour, ecology and physiology. Sex identification in the Critically Endangered European eel ( Anguilla anguilla ) currently requires fish sacrifice, or the use of morphological differences such as body length, which can be inaccurate in certain habitats and at intermediate body lengths. Non‐lethal tools for accurate sex identification in this species are therefore required. Here, we test the efficacy of two minimally invasive methods of sex identification: (1) ultrasonography and (2) molecular markers taken from pectoral fin clips. Both methodologies were applied to riverine European silver eel and compared to histological sex identification. Ultrasonography accurately identified the gonads in female eel, with males identified by the absence of detectable gonadal structures. The level of expression of three molecular markers ( dcn, LOC111853410 , kera ) previously used to identify sex in Japanese eel ( Anguilla japonica ) were evaluated. There was no significant differential expression of the three molecular markers between sexes, suggesting that these markers cannot be accurately used to identify sex in European eel. Our findings suggest that minimally invasive imaging using ultrasonography can be a reliable tool for identifying sex in early‐stage adult migratory European eels, with particular use at intermediate sizes (400–500 mm) and animals in habitats where migration potential is limited and may regularly exceed typical growth sizes. This technique can be highly valuable for studies that address ecological, behavioural, conservation and management issues in this Critically Endangered species.

Glaciation of the eastern Himalayas: Palaeoglacial and palaeoclimatic insights from the Dibang Valley, India - Shashank Nitundil; Christopher M. Darvill; Abi Stone; David Fink; Philip D. Hughes; Matt D. Tomkins; Krista Simon (Quaternary Science Reviews, 2026)

Mangrove sediments reveal drivers of Late Holocene sea-level change in the equatorial Pacific Ocean - Juliet P. Sefton; Andrew C. Kemp; Simon E. Engelhart; Matthew J. Brain; Joanna C. Ellison; Roger Creel; Christopher G. Piecuch; Robert E. Kopp; Blair Charley; Saimon Lihpai (Quaternary Science Reviews, 2026)

Correspondence between stated and operational preferences – An examination of overall liking, preference rankings, and three methods of takeaway choice - Adam Chismar; Christopher T. Simons (Food Quality and Preference, 2026)

Quantifying plant nutrient requirements in oil palm - Rana Farrasati; Walter Carciochi; Ya Li Lim; Christopher R. Donough; Juan Pablo Monzon; Hendra Sugianto; Dwi Asmono; Asad Ata; Rolf Härdter; Siti Mashilah Binti Abd Malik; Thomas Oberthür; Hafiz Ikhram Osman; et al. (European Journal of Agronomy, 2026)

Principles for ethical boundary spanning between science, policy and practice: A guide for knowledge brokers - Christopher Cvitanovic; Stefan Partelow; Angela Bednarek; Paul Cairney; Ramona Dalla Pozza; James Downe; Zelda Hilly; Anna-Katharina Hornidge; Mark Howden; Denis B. Karcher; Rachel Kelly; Nicole Klenk; et al. (Environmental Science & Policy, 2026)

Carbon Fluxes of Contrasting Degraded Peatland Pilot Sites During Early-stage Restoration: Ex-milled Bare Peat and Grazed Grassland Conversion - Anna T. Keightley; Christopher D. Field; Michael Longden; Simon J. M. Caporn (Environmental Management, 2026)
The recovery of degraded peatlands can make significant contributions to reducing greenhouse gas emissions and climate warming. This study examines restoration techniques on shallow ex-milled peatland and intensively grazed pasture on deeper peat, both subject to prior drainage. Carbon greenhouse gases (GHGs) were monitored for 3 years following restoration treatment. After drainage-blocking measures, the ex-milled peatland was ‘companion planted’ with Eriophorum species and Sphagnum . The carbon balance was highly dependent on plant age and condition, with a high CO 2 equivalent (CO 2 e) uptake when plants were vigorously growing (year 1: −22.4 ± 32.9 t CO 2 e ha −1 yr −1 ), and high emission when plants were mature and in various stages of senescence (year 2: 26.1 ± 26.4 and year 3: 16.4 ± 9.7 t CO 2 e ha −1 yr −1 ). Bare peat controls had a mean emission of 6.21 ± 1.68 t CO 2 e ha −1 yr −1 over the study period. At the other site, the grazed pasture was stripped, the bare surface planted with Sphagnum plugs, and irrigation was intensively managed via bunding, ditches, and automatic water pumping. Carbon GHG emissions were significantly reduced on this ‘carbon farm’ (2.77 ± 0.95 t CO 2 e ha −1 yr −1 ) compared to a neighbouring drained, grazed pasture control (31.7 ± 10.3 t CO 2 e ha −1 yr −1 ) over the study period (mean ± SD throughout). It appears clear that the cyclical nature of Eriophorum plant growth may only deliver carbon benefits on shallow peat over the long term if groundwater levels can be adequately supported and if climatic conditions are favourable. Conversion of grazed pasture to wetter farming crops, such as Sphagnum , can potentially deliver immediate carbon benefits, although, in this pilot, any potential loss of CO 2 e due to degraded topsoil removal, creation of bunds and irrigation ditches was not accounted for.

Fungus-resistant grape cultivars have up to threefold lower environmental impacts than traditional varieties - Claudio Petucco; Marie-Sophie Roderich; Daniel Molitor; Kristina Heilemann; Christopher Simon; Benedetto Rugani; Marco Beyer (Science of The Total Environment, 2026)

Transforming food authenticity testing by the exploitation of a machine learning – Data fusion approach: a tea case study - Yicong Li; Natasha Logan; Awanwee Petchkongkaew; Yunhe Hong; Xiaotong Liu; Nicholas Birse; Simon Haughey; Terry F. McGrath; Di Wu; Christopher T. Elliott (Food Chemistry, 2026)

Lithospheric mantle cooling recorded by zoned diamonds: forward modelling the nitrogen aggregation thermometer - Matthew M. Wincott; Laura Speich; Galina P. Bulanova; Ian J. Parkinson; Christopher B. Smith; Simon C. Kohn (Earth and Planetary Science Letters, 2026)

Extensive titanium isotope fractionation in magmatic and hydrothermal mineral systems - Christopher Emproto; Ryan Mathur; Adam C. Simon; Linda Godfrey; Jeffrey D. Vervoort; Mingguang Sun; Courteney Dhnaram; Vladimir Lisitsin; Martin Reich; Fernando Barra (Chemical Geology, 2026)

Developing and ranking a national red list of Saudi Arabian plants through meta-analysis - Christopher Clarke; Zahra Alhawsa; Simon John Attwood; Sarah Alsaidalani; Mark Tester (Biological Conservation, 2026)

Particulate nitrate over the Northwest Atlantic: Insights gained by comparing airborne AMS and PILS measurements - Soodabeh Namdari; Taiwo Ajayi; Yonghoon Choi; Ewan C. Crosbie; Joshua P. DiGangi; Glenn S. Diskin; Eva-Lou Edwards; Johnathan W. Hair; Christopher A. Hostetler; Simon Kirschler; John B. Nowak; Michael Shook; et al. (Atmospheric Environment, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

deadtrees.earth — An open-access and interactive database for centimeter-scale aerial imagery to uncover global tree mortality dynamics - Clemens Mosig; Janusch Vajna-Jehle; Miguel D. Mahecha; Yan Cheng; Henrik Hartmann; David Montero; Samuli Junttila; Stéphanie Horion; Mirela Beloiu Schwenke; Michael J. Koontz; Khairul Nizam Abdul Maulud; Stephen Adu-Bredu; et al. (Remote Sensing of Environment, 2026)

Portable NIR spectrometer and FTIR and soft modelling to authenticate edible cricket, mealworm and buffalo worm flour - J.P. Cruz-Tirado; Simon A. Haughey; Christopher T. Elliott; Douglas Fernandes Barbin (Food Control, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Two contrasting swamp forest succession pathways in central Congo Basin peatlands - Donna Hawthorne; Ian T. Lawson; Greta C. Dargie; Nicholas T. Girkin; Bart Crezee; William Hiles; George E. Biddulph; Yannick E. Bocko; Arnoud Boom; Corneille E.N. Ewango; Yannick Garcin; Pauline Gulliver; et al. (Quaternary Science Reviews, 2025)

The impact of climate change on the flux and fate of metals in freshwater systems: Implications for metal exposure across different scales - Farhan R. Khan; Nicolas R. Bury; Christopher A. Cooper; David Boyle; Elizabeth Middleton; Simon D. Herzog (Environmental Research, 2025)

Urban surface water flows contribute more PFAS to marine environments than treated wastewater - Phoebe Lewis; Erica Odell; Christopher P. Johnstone; Timothy Chaston; Daniel MacMahon; Tanya Paige; Simon Sharp; Mark Patrick Taylor; Vincent Pettigrove; Minna Saaristo (Environmental Research, 2025)

Community structure and microhabitat associations of cryptobenthic reef fishes in Veracruz, Mexico - Mariana Rivera-Higueras; Christopher R. Hemingson; Aurora de Monserrat Pouchoulen Alemán; Kyra Jean M. Cipolla; Philip M. Souza; Simon J. Brandl (Coral Reefs, 2025)

Ecological and Evolutionary Factors Shape the Extra‐Tropical Latitudinal Species Diversity Peak in Procellariiform Seabirds - Elize Y. X. Ng; Simon Wotherspoon; Louise Emmerson; Christopher P. Burridge (Journal of Biogeography, 2025)
Aim Latitudinal diversity gradients are common across broad taxonomic groups, with most exhibiting peak species richness in the tropics. These have often been explained by greater primary productivity and diversification rates in the tropics. However, some taxa show peak species richness outside the tropics, providing valuable contrasts for improving our understanding of the factors driving latitudinal diversity gradients. In this study, we tested ecological and evolutionary predictors of latitudinal diversity in Procellariiform seabirds, which exhibit peak species richness at temperate Southern Hemisphere latitudes. Location Global. Time Period Paleogene to present. Major Taxa Studied Order Procellariformes (Seabirds). Methods We assessed the latitudinal diversity gradient for Procellariiformes in the context of ecological factors including ocean productivity, ocean area, wind speed, and number of coastlines for breeding. We simultaneously tested evolutionary factors comprising lineage ages and transition and diversification rates among latitudes. Results While most ecological factors were retained in a Generalised Additive Model, wind appeared positively and most closely related to latitudinal breeding species richness. There was no evidence that unequal evolutionary transitions or diversification explained the latitudinal diversity gradient. However, an approximately two‐fold earlier origin in the Southern Temperate zone likely provided more time for species accumulation there. Main Conclusion Wind and time since evolutionary origin best explain the extratropical peak in breeding species richness of Procellariiform seabirds, emphasising the importance of integrating ecological and evolutionary perspectives when investigating latitudinal diversity gradients. Additionally, our study also illustrates how quantification of species distributions and the choice of phylogeny when testing evolutionary predictors can influence interpretations of latitudinal diversity gradients.

Comparison of ratings based and choice based approaches at integrating sensory attributes with extrinsic product attributes - Samuel Hoffman; Guilherme Signorini; Christopher T. Simons (Food Research International, 2025)

Capability of commercial cleaning procedures to remove food allergens from differing food contact materials and containers using sesame as a target analyte - Christopher A. James; Helen E. Arrowsmith; Marie-Anne L. Clarke; Simon Welham; Peter Rose (Journal of Food Engineering, 2025)

Determination of Toxic Tropane Alkaloids in Globally Sourced Soya, Cereals and Products Using Dilute-and-Shoot Technique Coupled with LC-MS/MS - Rufielyn S. Gravador; Brett Greer; Simon A. Haughey; M. Mar Aparicio-Muriana; Wilfred A. Abia; Alexandra-Irina Mavrochefalos; Anne P. Nugent; Christopher T. Elliott (Exposure and Health, 2025)
For the first time, this study reports the content of tropane alkaloids (TAs) in soybean and soymeal samples sourced from 13 different countries, as well as in various cereals (including corn, millet, wheat, and sorghum) and a product (Super Cereals). The analysis was conducted using a fully validated solid-liquid extraction (SLE) with dilute-and-shoot (DnS) method along with a liquid chromatography-tandem mass spectrometry (LC-MS/MS) triple quadrupole system. The samples were extracted using a solution of acetonitrile and water (60:40) with 1% formic acid. The limits of quantification (LOQ) were 0.10 µg kg −1 and 0.25 µg kg −1 for atropine and scopolamine, respectively. The extraction recovery was at least 80%, and the intra- and inter-day precision (relative standard deviation) were below 15% at 1, 5, and 50 µg kg −1 atropine and scopolamine spiked levels. The validation parameters showed that the method was fit for the purpose of accurate LC-MS/MS quantification of atropine and scopolamine. The SLE with DnS is high-throughput, enabling the extraction of TAs in 2.3 min per sample or at least 60 samples in 140 min. Whereas typical TA extraction methods require lengthy and costly clean-up and concentration steps, the DnS does not require these steps, sophisticated equipment, or an expert operator for execution, which makes it a simpler and straightforward procedure for TA analysis in different grain-based food matrices. Application of the LC-MS/MS method showed that one in 80 millet or corn, 18 in 269 soybeans, 20 in 62 soymeal and 20 in 42 Super Cereals samples had atropine and scopolamine above the maximum level of 1 μg kg −1 set by the EU Commission Regulation. TA contamination in these samples could either be due to the mixing with (visible) or exposure to (invisible) TA-producing plant material. The latter was proven through an exposure experiment, which showed that atropine and scopolamine from Datura stramonium seeds can be transferred to food grains (soybeans) invisibly with prolonged contact.

Tackling temporary names: interim solutions for the taxonomic impediment - Tammy Horton; Muriel Rabone; Shane T. Ahyong; Rüdiger Bieler; Christopher B. Boyko; Simone N. Brandão; Gustav Paulay; Erik Simon-Lledó; Ben Boydens; Wim Decock; Stefanie Dekeyzer; Lynn Delgat; et al. (Marine Biodiversity, 2025)
Against a background of the climate and biodiversity crises, there is an urgent need for robust and citable biodiversity information for policy and management decisions. Species are fundamental units of biodiversity and underpin communication in biology. Delineating, describing, and naming species provide the foundation for tracking biodiversity. Taxonomists recognise over 2 million described species, the scientific names of which follow provisions of codes of nomenclature, providing stability for communication about biodiversity. However, described species represent only a fraction of global biodiversity. Current advances in the fields of molecular biology and the growing use of image-based identifications have resulted in an explosion of informal species names globally, herein referred to as temporary names, increasing the rate of discovery of undescribed species and cryptic species complexes. We define two categories of temporary names: Type 1 names that are delineated in a local context but not further assessed; and Type 2 names that have been taxonomically assessed and recognised as either new or part of an unresolved species complex. We explore the different types and uses of temporary names, indicate how they can be managed in a robust and standardised manner and demonstrate how biodiversity databases, such as WoRMS, can be expanded to allow the tracking of both formal and informal scientific names. We propose a solution for the expanding problem of temporary names by defining and recommending the addition of Type 2 temporary names to nomenclatural databases such as WoRMS. We provide practical recommendations on how such names should be selected for entry and then entered to databases in a standardised way. These recommendations are a small step forward, but their broad adoption would support the robust integration of informal and formal taxonomies.

Assessing extensive pasture-based beef production in South Africa under future climate change conditions - Christopher Magona; Abubeker Hassen; Eyob Tesfamariam; Michael Mengistu; Carina Visser; Simon Oosting; Aart van der Linden (Agricultural Systems, 2025)

Environmental and Geographic Conditions on the Breeding Grounds Drive Bergmannian Clines in Nightjars - Aaron A. Skinner; Alicia M. Korpach; Susanne Åkesson; Marja H. Bakermans; Erin M. Bayne; Thomas J. Benson; Giovanni Boano; R. Mark Brigham; Simon S. Christiansen; Greg J. Conway; Christina M. Davy; Ruben Evens; et al. (Journal of Biogeography, 2025)
Aim To evaluate (1) whether three migratory nightjar species (Family Caprimulgidae) adhere to Bergmann's rule, (2) whether environmental factors on the breeding or wintering grounds determine body size, and (3) which mechanistic hypotheses best explain Bergmannian patterns in body size. Location North and South America; Europe and Africa. Taxon Eastern whip‐poor‐will ( Antrostomus vociferus ), Common nighthawk ( Chordeiles minor ) and European nightjar ( Caprimulgus europaeus ). Methods We used GPS tracking and morphometric data to assess competing hypotheses explaining variation in body size for each species, based on their breeding ( n = 3388) and wintering ( n = 189) locations. Results All three species exhibited Bergmannian patterns in body size, providing the first evidence that nightjars conform to Bergmann's rule despite adaptations to severe environmental conditions. Environmental and geographic variables at breeding sites were stronger predictors of body size than wintering‐site variables. Although we found partial support for Bergmann's temperature regulation hypothesis, geographic variables, rather than specific environmental factors, emerged as the strongest predictors of body size variation. Main Conclusions Latitude and longitude correlated strongly with environmental variables and migratory distance; thus, these geographical variables likely encompass many factors that influence body size in nightjars. The present study is among the first to use tracking data from individual birds to understand how environmental pressures across the annual cycle are related to body size. Our findings highlight the critical role of geographic breeding‐ground factors in shaping Bergmannian patterns, offering robust evidence to support nearly two centuries of research since Bergmann's rule was first described in 1847.

A Framework for Dynamic Assessment of Terrestrial Ecosystem Condition - Jinyan Yang; Yiqing Guo; Christopher J. Owers; Kate Giljohann; Roozbeh Valavi; Randall Donohue; Kristen J. Williams; Simon Ferrier; Karel Mokany (Global Ecology and Biogeography, 2025)
Aim The condition of terrestrial ecosystems (i.e., structure, function and composition) has been altered by increasing human pressure globally, affecting biodiversity and the sustainability of services that ecosystems provide. Effective conservation and restoration decisions will be supported by a continuous global fine‐scale assessment of changes in ecosystem condition over time. Innovation We developed a framework to provide annual ecosystem condition assessment based on remotely sensed ecosystem condition variables. Our conceptually simple approach compares the ecosystem variables of a target site to training sites with known condition. The comparison yields an ecosystem condition score as the similarity to the training sites. This framework provides a way to identify the temporal change in ecosystem condition while accommodating the natural dynamics of ecosystems and the spatial change from alternative natural states of ecosystems. Main Conclusions As a case study, we mapped annual ecosystem condition across Australia from 2013 to 2022, using Landsat‐derived condition variables at 100 m resolution. Our approach estimated ecosystem condition with high accuracy (RMSE = 0.23), which remained consistent along large environmental gradients. When evaluated against independent field‐based observations and other condition maps, our approach showed high agreement and identified the trajectories of ecosystem condition over time for sites with known changes. The case study suggests our approach is a useful tool to assess and monitor annual changes in ecosystem condition at continental scales. Our maps provide the information needed for assessing long‐term anthropogenic impacts on ecosystem condition and to support policy, planning and management decisions.

Magnesian-suite volcanism and ancient crust building on the Moon 4.25 billion years ago - Christopher Yen; Cécile Deligny; Bradley Jolliff; Alexander Nemchin; Paul Carpenter; Martin Whitehouse; Renaud Merle; Ryan Ogliore; Jeremy Kent; Ryan Zeigler; Juliane Gross; Scott Eckley; et al. (Earth and Planetary Science Letters, 2025)

ATMOCIAD: the ATomic and MOlecular cross-section for ionization and aurora database - Guillaume Gronoff; Cyril Simon Wedlund; Bradley Hegyi; Jean Lilensten; Alex Glocer; Gaël Cessateur; Olivier Witasse; Christopher J. Mertens (Advances in Space Research, 2025)

Investigating the effect of protein type and protein concentration on texture and mouthfeel sensory properties of plant and animal-based beverages - Min Sung Kim; Laura Nattress; Christopher T. Simons (Food Quality and Preference, 2025)

Development of a Detailed Finite Element Model of the BIPED MK2 and Verification of Fidelity in Two Cases of Blunt Impact - Robert Chauvet; Ashton Martin; Jennifer Rovt; Oren Petel; Simon Ouellet; Lindsey Westover; Christopher R. Dennison (Annals of Biomedical Engineering, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Tropical Land‐Use Change Disrupts Zeta‐Diversity Across Taxa - Edicson Parra‐Sanchez; Guillaume Latombe; Simon C. Mills; Jacob B. Socolar; Felicity A. Edwards; Diego Martinez‐Revelo; Oscar A. Perez‐Escobar; Robert W. Davies; Christopher G. Bousfield; Gianluca R. Cerullo; Jose Manuel Ochoa‐Quintero; Torbjørn Haugaasen; et al. (Global Change Biology, 2025)
Land‐use change causes community turnover via local extinction and colonisation of species, driving biotic homogenization or heterogenization at larger spatial scales. Quantification of these processes has focused on beta‐diversity metrics, which upweight rarity and overlook the role of widespread species. A key knowledge gap is understanding the impact of land‐use change on both rare and widespread species—zeta‐diversity—allowing the detection of statistical patterns and drivers based on community turnover across space. We sampled bird, dung beetle, and orchid communities in 341 plots across natural (Andean forests and paramo) and transformed habitats (pasturelands) spanning ~270 km north‐to‐south in the Colombian Andes. We detected major losses in species richness following land‐use conversion, which disrupts zeta‐diversity across elevation in two ways. First, biodiversity patterns are rewired such that bird and dung beetle communities become structured by dispersal ability, overriding the effects of natural biogeographical drivers (i.e., elevation) and landscape conditions (i.e., canopy cover). Second, land‐use change causes biotic homogenization across bird communities, with pasture retaining twice as many widespread species than natural habitats, and a four‐fold reduction in widespread dung beetle species pointing to subtractive heterogenization. Orchid communities show high community turnover in both natural and transformed habitat. Our results show that the effect of local deforestation has a doubly devastating impact simplifying communities and reducing widespread species. Transforming natural habitats into anthropogenic landscapes may substantially raise extinction risk for communities composed of both widespread and rare species, especially in orchids as the most sensitive taxon.

Do carotenoids protect phytodetritus-associated bacteria from oxidative stress? - Gwénola Simon; Laurie Casalot; Corinne Valette; Christopher Burot; Jean François Rontani; Patricia Bonin (Environmental Science and Pollution Research, 2025)

The temperature dependence of greenhouse gas production from Central African savannah soils - Nicholas T. Girkin; Hannah V. Cooper; Alice S. Johnston; Martha Ledger; G.R. Mouanda Niamba; Christopher H. Vane; Vicky Moss-Hayes; Dafydd Crabtree; Greta C. Dargie; Saul Vasquez; Yannick Bocko; Emmanuel Mampouya Wenina; et al. (Geoderma Regional, 2025)

Deep-sea drilling of the 13°30′ N oceanic core complex: Assessing links between fluid flow, metal enrichment and seafloor massive sulfide deposit formation near Semenov-1 - Andrew J. Martin; Bramley J. Murton; Christopher J. MacLeod; John W. Jamieson; Isobel I. Yeo; Sven Petersen; Katie A. McFall; Simon Allerton; Anna Lichtschlag; Christian Bishop; Acer Figueroa; Szu-Ying Lai (Lithos, 2025)

Fluid-mineral titanium isotope fractionation: Computational and empirical results with implications for mineral deposits - Christopher Emproto; Ryan Mathur; Mingguang Sun; Adam C. Simon; Linda Godfrey (Geochimica et Cosmochimica Acta, 2025)

Legume protein gelation: The mechanism behind the formation of homogeneous and fractal gels - Alice Y.J. Tiong; Simon Crawford; Liliana de Campo; Vasyl Ryukhtin; Christopher J. Garvey; Warren Batchelor; Leonie van ’t Hag (Food Hydrocolloids, 2025)

Seroprevalence and risk factors for Toxoplasma gondii exposure in Australian feral and stray cats using an in-house modified agglutination test - K.L.D. Tharaka D. Liyanage; Jemima Amery-Gale; Alessandro D. Uboldi; Katherine Adriaanse; Simon M. Firestone; Christopher J. Tonkin; Abdul Jabbar; Jasmin Hufschmid (Veterinary Parasitology, 2024)

Enabling efficient satellite mission design with rule-based collision avoidance - Simon Burgis; Pia Lenhardt; Reinhold Bertrand; Esfandiar Farahvashi; Jonas Radtke; Christopher Kebschull (Journal of Space Safety Engineering, 2024)

Lineage diversity in a Melanesian lizard radiation (Gekkonidae: Nactus) further highlights exceptional diversity and endemism in eastern Papua New Guinea - Paul M. Oliver; Fred Kraus; Christopher C. Austin; Leonardo G. Tedeschi; Aurora R. O’Brien; Simon T. Maddock (Organisms Diversity & Evolution, 2024)
New Guinea and surrounding islands are home to some of the richest assemblages of insular biodiversity in the world. The key geological drivers of species richness in this region are largely considered to be mountain uplift and development of offshore archipelagos—some of which have accreted onto New Guinea—with the role of mountain uplift and elevational gradients receiving more attention than the role of isolation on islands. Here, we examine the distribution of lineage richness and body-size diversity in a radiation of Melanesian lizards that is almost entirely absent from montane habitats but closely associated with islands—the geckos of the genus Nactus . Our data indicate that eastern New Guinea—centred on the East Papuan Composite Terrane (EPCT)—shows particularly high levels of endemism and body-size diversity and is also inferred to be a source area for multiple independent colonisations elsewhere in New Guinea, the Pacific and Australia. Two Nactus lineages in Australia have closest relatives occurring to the north of New Guinea’s Central Cordillera, suggesting dispersal through this area in the mid-Miocene, possibly via seaways that would have isolated the islands to the east and west of the proto-Papuan region. Syntopic species tend to differ in body length; however, at a phylogenetic scale, this trait appears to be conservative, with small-sized and large-sized species clustered into separate lineages. These data suggest that species richness in Melanesian Nactus is in part explained by morphological diversification enabling the presence of sympatric communities to exist, but to a greater extent by multiple instances of dispersal and extensive allopatric and parapatric speciation, especially in and around the islands of the EPCT.

Effects of climate warming on energetics and habitat of the world's largest marine ectotherm - Samantha D. Reynolds; Craig E. Franklin; Bradley M. Norman; Anthony J. Richardson; Jason D. Everett; David S. Schoeman; Craig R. White; Christopher L. Lawson; Simon J. Pierce; Christoph A. Rohner; Steffen S. Bach; Francesco G. Comezzi; et al. (Science of The Total Environment, 2024)

Feedback control of apple juice quality during storage via multiple, mild in-situ processing treatments - Jin Hong Mok; Taras Pyatkovskyy; Brian Heskitt; Ashley Soldavini; Christopher T. Simons; Ahmed Yousef; Sudhir K. Sastry (Journal of Food Engineering, 2024)

Forecasting dead fuel moisture content below forest canopies – A seven-day forecasting system - Christopher Sean Lyell; Usha Nattala; Thomas Keeble; Elena M. Vella; Rakesh Chandra Joshi; Zaher Joukhadar; Jonathan Garber; Simon J Mutch; Tim Gazzard; Tom Duff; Gary Sheridan (Agricultural and Forest Meteorology, 2024)

A sustainable blue economy may not be possible in Tanzania without cutting emissions - Ana M. Queirós; Elizabeth Talbot; Flower E. Msuya; Baraka Kuguru; Narriman Jiddawi; Shigalla Mahongo; Yohana Shaghude; Christopher Muhando; Elias Chundu; Zoe Jacobs; Sevrine Sailley; Elina A. Virtanen; et al. (Science of The Total Environment, 2024)

“That Looks Like My Kitchen!” − Personalized context by usage frequency and familiarity influences consumer perception and liking of chicken nuggets in VR - Kym Man; Jeremy A. Patterson; Christopher T. Simons (Food Research International, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

Defining an ageing-related pathology, disease or syndrome: International Consensus Statement - Emma Short; Ian M. Adcock; Bilal Al-Sarireh; Ann Ager; Ramzi Ajjan; Naveed Akbar; Michael A. Akeroyd; Ghada Alsaleh; Ghada Al-Sharbatee; Kambiz Alavian; Winfried Amoaku; Julie Andersen; et al. (GeroScience, 2024)
Around the world, individuals are living longer, but an increased average lifespan does not always equate to an increased health span. With advancing age, the increased prevalence of ageing-related diseases can have a significant impact on health status, functional capacity and quality of life. It is therefore vital to develop comprehensive classification and staging systems for ageing-related pathologies, diseases and syndromes. This will allow societies to better identify, quantify, understand and meet the healthcare, workforce, well-being and socioeconomic needs of ageing populations, whilst supporting the development and utilisation of interventions to prevent or to slow, halt or reverse the progression of ageing-related pathologies. The foundation for developing such classification and staging systems is to define the scope of what constitutes an ageing-related pathology, disease or syndrome. To this end, a consensus meeting was hosted by the International Consortium to Classify Ageing-Related Pathologies (ICCARP), on February 19, 2024, in Cardiff, UK, and was attended by 150 recognised experts. Discussions and voting were centred on provisional criteria that had been distributed prior to the meeting. The participants debated and voted on these. Each criterion required a consensus agreement of ≥ 70% for approval. The accepted criteria for an ageing-related pathology, disease or syndrome were (1) develops and/or progresses with increasing chronological age; (2) should be associated with, or contribute to, functional decline or an increased susceptibility to functional decline and (3) evidenced by studies in humans. Criteria for an ageing-related pathology, disease or syndrome have been agreed by an international consortium of subject experts. These criteria will now be used by the ICCARP for the classification and ultimately staging of ageing-related pathologies, diseases and syndromes.

In-situ observations of resident space objects with the CHEOPS space telescope - Nicolas Billot; Stephan Hellmich; Willy Benz; Andrea Fortier; David Ehrenreich; Christopher Broeg; Alexis Heitzmann; Anja Bekkelien; Alexis Brandeker; Yann Alibert; Roi Alonso; Tamas Bárczy; et al. (Journal of Space Safety Engineering, 2024)

Microstructural control on the trace element distribution and Au concentration in pyrite nodules - Riccardo Graziani; Duane C. Petts; Jean-Luc Pilote; Simon E. Jackson; Daniele Regis; Christopher J.M. Lawley; Matthew Polivchuk; Yannick Bussweiler; Martin Rittner (Geochemistry, 2024)

Evaluation of food allergen information, labelling and unintended food allergen presence in imported prepacked foods and drinks purchased online in the UK - Christopher A. James; Simon Welham; Peter Rose (Food Control, 2024)

Evolution of white matter hyperintensity segmentation methods and implementation over the past two decades; an incomplete shift towards deep learning - Maryam Rahmani; Donna Dierker; Lauren Yaeger; Andrew Saykin; Patrick H. Luckett; Andrei G. Vlassenko; Christopher Owens; Hussain Jafri; Kyle Womack; Jurgen Fripp; Ying Xia; Duygu Tosun; et al. (Brain Imaging and Behavior, 2024)
This systematic review examines the prevalence, underlying mechanisms, cohort characteristics, evaluation criteria, and cohort types in white matter hyperintensity (WMH) pipeline and implementation literature spanning the last two decades. Following Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) guidelines, we categorized WMH segmentation tools based on their methodologies from January 1, 2000, to November 18, 2022. Inclusion criteria involved articles using openly available techniques with detailed descriptions, focusing on WMH as a primary outcome. Our analysis identified 1007 visual rating scales, 118 pipeline development articles, and 509 implementation articles. These studies predominantly explored aging, dementia, psychiatric disorders, and small vessel disease, with aging and dementia being the most prevalent cohorts. Deep learning emerged as the most frequently developed segmentation technique, indicative of a heightened scrutiny in new technique development over the past two decades. We illustrate observed patterns and discrepancies between published and implemented WMH techniques. Despite increasingly sophisticated quantitative segmentation options, visual rating scales persist, with the SPM technique being the most utilized among quantitative methods and potentially serving as a reference standard for newer techniques. Our findings highlight the need for future standards in WMH segmentation, and we provide recommendations based on these observations.

Reimagining the language of engagement in a post-stakeholder world - Mark S. Reed; Bethann Garramon Merkle; Elizabeth J. Cook; Caitlin Hafferty; Adam P. Hejnowicz; Richard Holliman; Ian D. Marder; Ursula Pool; Christopher M. Raymond; Kenneth E. Wallen; David Whyte; Marta Ballesteros; et al. (Sustainability Science, 2024)
Language matters in shaping perceptions and guiding behaviour. The term stakeholder is widely used, yet little attention is paid to the possibility that its use may inadvertently perpetuate colonial narratives and reinforce systemic inequities. In this article, we critically examine the limitations of the stakeholder concept and its ambiguity, normativity, and exclusionary implications. We emphasise the importance of using language that gives a voice to marginalised groups, promotes inclusion and equity, and fosters meaningful and reflexive participation in decision-making processes. In critiquing the use of the term and calling for alternative practices, we aim to contribute to the decolonisation of research norms and the creation of more inclusive and equitable societies. Therefore, rather than advocating a single alternative term, we suggest a focus on the people, places, and species affected by decisions, interventions, projects, and issues.

Epigenetic age acceleration is a distinctive trait of epithelioid sarcoma with potential therapeutic implications - Simon Haefliger; Olga Chervova; Christopher Davies; Chet Loh; Roberto Tirabosco; Fernanda Amary; Nischalan Pillay; Steve Horvath; Stephan Beck; Adrienne M. Flanagan; Iben Lyskjær (GeroScience, 2024)
Recently, DNA methylation clocks have been proven to be precise age predictors, and the application of these clocks in cancer tissue has revealed a global age acceleration in a majority of cancer subtypes when compared to normal tissue from the same individual. The polycomb repressor complex 2 plays a pivotal role in the aging process, and its targets have been shown to be enriched in CpG sites that gain methylation with age. This complex is further regulated by the chromatin remodeling complex SWItch/Sucrose Non-Fermentable and its core subunit, notably the tumor suppressor gene SMARCB1 , which under physiological conditions inhibits the activity of the polycomb repressor complex 2. Hence, the loss of function of core members of the SWItch/sucrose non-fermentable complex, such as the tumor suppressor gene SMARCB1 , results in increased activity of polycomb repressor complex 2 and interferes with the aging process. SMARCB1 -deficient neoplasms represent a family of rare tumors, including amongst others malignant rhabdoid tumors, atypical teratoid and rhabdoid tumors, and epithelioid sarcomas. As aging pathways have recently been proposed as therapeutic targets for various cancer types, these tumors represent candidates for testing such treatments. Here, by deriving epigenetic age scores from more than 1000 tumor samples, we identified epigenetic age acceleration as a hallmark feature of epithelioid sarcoma. This observation highlights the potential of targeting aging pathways as an innovative treatment approach for patients with epithelioid sarcoma.

The impact of cannabinoids on methemoglobin formation and hemoglobin oxygen affinity: An ex-vivo study - Christoph Frisch; Simon Woyke; Norbert Mair; Thomas Haller; Marco Ronzani; Katharina Marcher; Dominik Schantl; Christopher Rugg; Andreas Schlager (Toxicology, 2024)

Using luminescence dating to constrain lake sediment records: A new age model for the 1.38 Ma lake Malawi drill core, Eastern Africa - Laura C. Streib; Simon J. Armitage; Christopher A. Scholz (Quaternary Science Reviews, 2024)

Ulvans are not equal - Linkage and substitution patterns in ulvan polysaccharides differ with Ulva morphology - Joel T. Kidgell; Christopher R.K. Glasson; Marie Magnusson; Ian M. Sims; Simon F.R. Hinkley; Rocky de Nys; Susan M. Carnachan (Carbohydrate Polymers, 2024)

Taraxerol abundance as a proxy for in situ mangrove sediment - Juliet P. Sefton; Andrew C. Kemp; Christopher H. Vane; Alexander W. Kim; Christopher E. Bernhardt; Jonathan Johnson; Simon E. Engelhart (Organic Geochemistry, 2024)

Revisiting the discrimination and distribution of S-type granites from zircon trace element composition - Nick M W Roberts; Chris Yakymchuk; Christopher J Spencer; C. Brenhin Keller; Simon R Tapster (Earth and Planetary Science Letters, 2024)

Simulation of national-scale groundwater dynamics in geologically complex aquifer systems: an example from Great Britain - Marco Bianchi; Johanna Scheidegger; Andrew Hughes; Christopher Jackson; Jonathan Lee; Melinda Lewis; Majdi Mansour; Andrew Newell; Brighid O’Dochartaigh; Ashley Patton; Simon Dadson (Hydrological Sciences Journal, 2024)

Fingerprinting black tea: When spectroscopy meets machine learning a novel workflow for geographical origin identification - Yicong Li; Natasha Logan; Brian Quinn; Yunhe Hong; Nicholas Birse; Hao Zhu; Simon Haughey; Christopher T. Elliott; Di Wu (Food Chemistry, 2024)

Correction to: The Kelp Forest Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh‑Dalmau; Nina Larissa Arroyo; Anne M. Bauer‑Civiello; Rodrigo Beas‑Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)

The Kelp Forest ﻿Challenge: A collaborative global movement to protect and restore 4 million hectares of kelp forests - Aaron Eger; J. David Aguirre; María Altamirano; Nur Arafeh-Dalmau; Nina Larissa Arroyo; Anne M. Bauer-Civiello; Rodrigo Beas-Luna; Trine Bekkby; Alecia Bellgrove; Scott Bennett; Blanca Bernal; Caitlin O. Blain; et al. (Journal of Applied Phycology, 2024)
Marine kelp forests cover 1/3 of our world's coastlines, are heralded as a nature-based solution to address socio-environmental issues, connect hundreds of millions of people with the ocean, and support a rich web of biodiversity throughout our oceans. But they are increasingly threatened with some areas reporting over 90% declines in kelp forest cover in living memory. Despite their importance and the threats they face, kelp forests are entirely absent from the international conservation dialogue. No international laws, policies, or targets focus on kelp forests and very few countries consider them in their national policy. The Kelp Forest Challenge addresses that gap. Together with 252 kelp experts, professionals, and citizens from 25 countries, the Kelp Forest Challenge was developed as a grassroots vision of what the world can achieve for kelp forest conservation. It is a global call to restore 1 million and protect 3 million hectares of kelp forests by 2040. This is a monumental challenge, that will require coordination across multiple levels of society and the mobilization of immense resources. Pledges may therefore include area for protection or restoration, enabling pledges which assist in conservation (funding, equipment, professional expertise, capacity building), or awareness-based pledges which increase awareness or education about kelp forests. Correspondingly, participants may be from government, scientific institutions, private sector, NGOs, community groups, or individuals. This challenge is the beginning of a 17-year mission to save our kelp forests and anyone and any organisation is invited to participate.

Cryptic diversification, phenotypic plasticity, and host specialization in a sponge-dwelling goby - Ariel Wang; Sarah Yerrace; Luke Tornabene; Simon J. Brandl; Christopher J. Freeman; Carole C. Baldwin; Jordan M. Casey (Coral Reefs, 2024)

Successful DNA amplification of DNA from non-destructive buccal swabbing in Vespertilionid and Rhinolophid bats - Morgan Hughes; Scott K Brown; Rémi Martin; Christopher H Young; Simon Maddock (Conservation Genetics Resources, 2024)
Acquiring DNA from wild bats (Mammalia: Chiroptera) is typically undertaken utilizing highly invasive (but non-lethal) sampling techniques comprising wing biopsies and occasional blood samples. While non-invasive sampling is possible through the extraction of DNA from faecal samples, it is not always possible to acquire samples from individual bats whilst conducting fieldwork, and as such, this method is primarily applicable to roost occupancy identification. Similarly, wing swabbing is liable to cross-contamination from roost mates. Here we present the first use of oral (buccal) swabbing for successful, species-resolution DNA sequencing of Vespertilionidae and Rhinolophidae in 10 bat species (nine Vespertilionidae and one Rhinolophidae) from the UK.

Correction: Evaluating the Intracranial Pressure Biofidelity and Response Repeatability of a Physical Head-Brain Model in Frontal Impacts - Yizhao Li; Paris Vakiel; Kevin Adanty; Simon Ouellet; Albert H. Vette; Donald Raboud; Christopher R. Dennison (Annals of Biomedical Engineering, 2024)

Elevated CO 2 interacts with nutrient inputs to restructure plant communities in phosphorus‐limited grasslands - Christopher R. Taylor; Luke C. England; J. Ben Keane; Jessica A. C. Davies; Jonathan R. Leake; Iain P. Hartley; Simon M. Smart; Victoria Janes‐Bassett; Gareth K. Phoenix (Global Change Biology, 2024)
Globally pervasive increases in atmospheric CO 2 and nitrogen (N) deposition could have substantial effects on plant communities, either directly or mediated by their interactions with soil nutrient limitation. While the direct consequences of N enrichment on plant communities are well documented, potential interactions with rising CO 2 and globally widespread phosphorus (P) limitation remain poorly understood. We investigated the consequences of simultaneous elevated CO 2 (eCO 2 ) and N and P additions on grassland biodiversity, community and functional composition in P‐limited grasslands. We exposed soil‐turf monoliths from limestone and acidic grasslands that have received >25 years of N additions (3.5 and 14 g m −2 year −1 ) and 11 (limestone) or 25 (acidic) years of P additions (3.5 g m −2 year −1 ) to eCO 2 (600 ppm) for 3 years. Across both grasslands, eCO 2 , N and P additions significantly changed community composition. Limestone communities were more responsive to eCO 2 and saw significant functional shifts resulting from eCO 2 –nutrient interactions. Here, legume cover tripled in response to combined eCO 2 and P additions, and combined eCO 2 and N treatments shifted functional dominance from grasses to sedges. We suggest that eCO 2 may disproportionately benefit P acquisition by sedges by subsidising the carbon cost of locally intense root exudation at the expense of co‐occurring grasses. In contrast, the functional composition of the acidic grassland was insensitive to eCO 2 and its interactions with nutrient additions. Greater diversity of P‐acquisition strategies in the limestone grassland, combined with a more functionally even and diverse community, may contribute to the stronger responses compared to the acidic grassland. Our work suggests we may see large changes in the composition and biodiversity of P‐limited grasslands in response to eCO 2 and its interactions with nutrient loading, particularly where these contain a high diversity of P‐acquisition strategies or developmentally young soils with sufficient bioavailable mineral P.

Essential omega‐3 fatty acids are depleted in sea ice and pelagic algae of the Central Arctic Ocean - Katrin Schmidt; Martin Graeve; Clara J. M. Hoppe; Sinhué Torres‐Valdes; Nahid Welteke; Laura M. Whitmore; Philipp Anhaus; Angus Atkinson; Simon T. Belt; Tina Brenneis; Robert G. Campbell; Giulia Castellani; et al. (Global Change Biology, 2024)
Microalgae are the main source of the omega‐3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), essential for the healthy development of most marine and terrestrial fauna including humans. Inverse correlations of algal EPA and DHA proportions (% of total fatty acids) with temperature have led to suggestions of a warming‐induced decline in the global production of these biomolecules and an enhanced importance of high latitude organisms for their provision. The cold Arctic Ocean is a potential hotspot of EPA and DHA production, but consequences of global warming are unknown. Here, we combine a full‐seasonal EPA and DHA dataset from the Central Arctic Ocean (CAO), with results from 13 previous field studies and 32 cultured algal strains to examine five potential climate change effects; ice algae loss, community shifts, increase in light, nutrients, and temperature. The algal EPA and DHA proportions were lower in the ice‐covered CAO than in warmer peripheral shelf seas, which indicates that the paradigm of an inverse correlation of EPA and DHA proportions with temperature may not hold in the Arctic. We found no systematic differences in the summed EPA and DHA proportions of sea ice versus pelagic algae, and in diatoms versus non‐diatoms. Overall, the algal EPA and DHA proportions varied up to four‐fold seasonally and 10‐fold regionally, pointing to strong light and nutrient limitations in the CAO. Where these limitations ease in a warming Arctic, EPA and DHA proportions are likely to increase alongside increasing primary production, with nutritional benefits for a non‐ice‐associated food web.

Population links between an insectivorous bird and moths disentangled through national‐scale monitoring data - Luke Christopher Evans; Malcolm D. Burgess; Simon G. Potts; William E. Kunin; Tom H. Oliver (Ecology Letters, 2024)
Insects are key components of food chains, and monitoring data provides new opportunities to identify trophic relationships at broad spatial and temporal scales. Here, combining two monitoring datasets from Great Britain, we reveal how the population dynamics of the blue tit Cyanistes caeruleus are influenced by the abundance of moths – a core component of their breeding diet. We find that years with increased population growth for blue tits correlate strongly with high moth abundance, but population growth in moths and birds is less well correlated; suggesting moth abundance directly affects bird population change. Next, we identify moths that are important components of blue tit diet, recovering associations to species previously identified as key food sources such as the winter moth Operoptera brumata . Our work provides new evidence that insect abundance impacts bird population dynamics in natural communities and provides insight into spatial diet turnover at a national‐scale.

A Preliminary Step Towards a Physical Surrogate of the Human Calvarium to Model Fracture - Kevin Adanty; Aaron Brice; Yizhao Li; Paris Vakiel; Karyne N. Rabey; Samer Adeeb; Simon Ouellet; Dan L. Romanyk; Christopher R. Dennison (Annals of Biomedical Engineering, 2023)

Optimising mechanical separation of anaerobic digestate for total solids and nutrient removal - Ashley Cathcart; Beatrice M. Smyth; Gary Lyons; Simon T. Murray; David Rooney; Christopher R. Johnston (Journal of Environmental Management, 2023)

Ethics of artificial intelligence in prenatal and pediatric genomic medicine - Simon Coghlan; Christopher Gyngell; Danya F Vears (Journal of Community Genetics, 2023)
This paper examines the ethics of introducing emerging forms of artificial intelligence (AI) into prenatal and pediatric genomic medicine. Application of genomic AI to these early life settings has not received much attention in the ethics literature. We focus on three contexts: (1) prenatal genomic sequencing for possible fetal abnormalities, (2) rapid genomic sequencing for critically ill children, and (3) reanalysis of genomic data obtained from children for diagnostic purposes. The paper identifies and discusses various ethical issues in the possible application of genomic AI in these settings, especially as they relate to concepts of beneficence, nonmaleficence, respect for autonomy, justice, transparency, accountability, privacy, and trust. The examination will inform the ethically sound introduction of genomic AI in early human life.

A Ceratopteris EXCESS MICROSPOROCYTES1 suppresses reproductive transition in the fern vegetative leaves - Kelley A. Withers; Kevin Falls; Christopher E. Youngstrom; Tommy Nguyen; Anika DeWald; Rebekah M. Yarvis; Gabriel P. Simons; Robert Flanagan; Linh T. Bui; Erin E. Irish; Chi-Lien Cheng (Plant Science, 2023)

Integrating risk assessment methods for carbon storage: A case study for the quest carbon capture and storage facility - Christopher F. Brown; Greg Lackey; Nate Mitchell; Seunghwan Baek; Brandon Schwartz; Marcella Dean; Robert Dilmore; Hein Blanke; Simon O'Brien; Carrie Rowe (International Journal of Greenhouse Gas Control, 2023)

Characterization of the impact of chlorogenic acids on tactile perception in coffee through an inverse effect on mouthcoating sensation - Brianne M. Linne; Edisson Tello; Christopher T. Simons; Devin G. Peterson (Food Research International, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Effect of degradation on geotechnical behavior of glauconite sands from the U.S. Mid-Atlantic Coastal Plain - Zachary J. Westgate; Don J. DeGroot; Christopher McMullin; Yuanjing Zou; Dongdong Guo; Simon Van Haren; Ryan D. Beemer; Danilo Zeppilli; Kenneth G. Miller; James V. Browning (Ocean Engineering, 2023)

Reducing the time-dependent climate impact of intensive agriculture with strategically positioned short rotation coppice willow - David Livingstone; Beatrice M. Smyth; Rachel Cassidy; Simon T. Murray; Gary A. Lyons; Aoife M. Foley; Christopher R. Johnston (Journal of Cleaner Production, 2023)

Identifying Gaps and Challenges in Global Pesticide Legislation that Impact the Protection of Consumer Health: Rice as a Case Study - Patricia Kubiak-Hardiman; Simon A. Haughey; Julie Meneely; Sarah Miller; Kaushik Banerjee; Christopher T. Elliott (Exposure and Health, 2023)
With continued global population expansion, food production will have to increase with crops protected against the growing menace of pests, requiring the increased use of pesticides globally to ensure that agricultural production is optimised and remains economically viable. The aim of this systematic review was to perform an in-depth analysis of pesticide legislation, focusing on rice, to understand the gaps that exist in the harmonisation across different countries. Tricyclazole, carbendazim, thiamethoxam and acephate were considered as these received the highest numbers of RASFF notifications and alerts due to their presence in rice. Global differences in regulations cause trade issues, especially when developing countries use unauthorised pesticides or different MRLs. Discrepancies in the registration and regulation of sales were found to be a global problem. Sales of pesticides and resulting residues in developing countries that are banned in the EU or US is highly concerning. Evidence suggests farmers’ education regarding pesticide use and protection must be increased, particularly as climate change is impacting pesticide use patterns and their bio-efficacy. In conclusion, international pesticide regulations have been implemented to protect consumer health, the environment and facilitate international trade. However, the absence of national MRLs in some countries or non-alignments with Codex MRLs raise significant concerns regarding some pesticides in relation to the protection of consumer health and the use of mixtures versus single pesticides. Additionally, global differences in pesticide regulation highlight problems in trade, especially when developing countries use unauthorised pesticides or when MRLs are not in agreement.

When considering whether to waste food, consumers focus attention on food label dates rather than phrases - Aishwarya Badiger; Talia Katz; Christopher T. Simons; Brian E. Roe (Waste Management, 2023)

Climate change and variability in sub-Saharan Africa: A systematic review of trends and impacts on agriculture - Abeeb Babatunde Omotoso; Simon Letsoalo; Kehinde Oluseyi Olagunju; Christopher Seleke Tshwene; Abiodun Olusola Omotayo (Journal of Cleaner Production, 2023)

Publisher Correction: Evaluating the Intracranial Pressure Biofidelity and Response Repeatability of a Physical Head-Brain Model in Frontal Impacts - Yizhao Li; Paris Vakiel; Kevin Adanty; Simon Ouellet; Albert H. Vette; Donald Raboud; Christopher R. Dennison (Annals of Biomedical Engineering, 2023)

Evaluating the Intracranial Pressure Biofidelity and Response Repeatability of a Physical Head-Brain Model in Frontal Impacts - Yizhao Li; Paris Vakiel; Kevin Adanty; Simon Ouellet; Albert H. Vette; Donald Raboud; Christopher R. Dennison (Annals of Biomedical Engineering, 2023)

Economics, morality, or race: Referenda voting on tribal gaming legalization - Christopher A. Simon; John Frendreis; Raymond Tatalovich (The Social Science Journal, 2023)

The impact of personally relevant consumption contexts during product evaluations in virtual reality - Kym Man; Jeremy A. Patterson; Christopher Simons (Food Quality and Preference, 2023)

The effects of gamification on engagement and response accuracy in discriminatory sensory testing - Jessica Miao; Christopher T. Simons (Food Quality and Preference, 2023)

Risk assessments for the dietary intake aflatoxins in food: A systematic review (2016–2022) - Kiran Bhardwaj; Julie P. Meneely; Simon A. Haughey; Moira Dean; Patrick Wall; Guangtao Zhang; Bob Baker; Christopher T. Elliott (Food Control, 2023)

The Challenge of Global Aflatoxins Legislation with a Focus on Peanuts and Peanut Products: A Systematic Review - Julie P. Meneely; Oluwatobi Kolawole; Simon A. Haughey; Sarah J. Miller; Rudolf Krska; Christopher T. Elliott (Exposure and Health, 2023)
Globally, of all mycotoxins, aflatoxins present a significant threat to human and animal health and has resulted in the introduction of strict food regulatory limits to protect public health. A systematic review, was performed to elucidate the rationale applied in establishing aflatoxin standards and evaluate the economic impacts of these. The focus was peanuts, a principal trading commodity susceptible to aflatoxin contamination. Results revealed that although regulations are established in many countries, there is huge disparity in the maximum limits applied due to different methodologies used when considering exposure assessment. Moreover, in countries most affected by aflatoxin contamination in peanuts, few, if any standards exist. In the case of risk assessments, knowledge gaps identified include the impact of climate change on peanut aflatoxin contamination, the role of aflatoxins in child stunting, Kwashiorkor and immunomodulation and a lack of occurrence and exposure data in many developing countries from contaminated peanuts. Few quantitative studies evaluating the impact of aflatoxin regulations on trade exist and evidence is lacking in terms of what happens to exports that do not meet regulatory requirements. Evidence does suggest a lack of knowledge of the extent of the aflatoxin problem, associated health risks and mitigation strategies in developing countries. A hugely important factor that needs to be highlighted is that while there is a fundamental right for sufficient, safe, nutritious food, in many cases in low-income and lower middle-income countries there exists an incredibly difficult and complex trade-off between food security and food safety.

The role of irradiance in controlling coralline algal calcification - Erik C. Krieger; Wendy A. Nelson; Johan Grand; Eric C. Le Ru; Sarah J. Bury; Amelie Cossais; Simon K. Davy; Christopher E. Cornwall (Limnology and Oceanography, 2023)
Coralline algae are an essential element of benthic ecosystems throughout the ocean's photic zone. Yet, the role of light in shaping the physiology of coralline algae from cold‐water, low‐light habitats is poorly understood. Here, we assess the calcification physiology of five cool temperate coralline algae in response to different irradiance levels over 3 months. We show that in contrast to current models focused on warmer water species, previously observed enhancement of calcification rates by photosynthesis is largely limited to lower irradiances, and that the removal of CO 2 from the calcifying fluid is not the underlying mechanism of this enhancement. Instead, this most likely occurs via two processes: (1) increased ion pumping rates to elevate the calcium carbonate saturation state in the calcifying fluid; and (2) a higher daytime pH in the diffusion boundary layer that raises calcifying fluid pH. However, as irradiance increases, ion pumping becomes increasingly saturated limiting further enhancements. Our results also suggest the existence of two calcification strategies in coralline algae and indicate that magnesium incorporation is determined by the magnesium to calcium ratio in the calcifying fluid ([Mg] CF /[Ca] CF ). This study adds to our mechanistic understanding of calcification in coralline algae and fills in much needed knowledge about the role of light in controlling their physiology.

Coral adaptive capacity insufficient to halt global transition of coral reefs into net erosion under climate change - Christopher Edward Cornwall; Steeve Comeau; Simon D. Donner; Chris Perry; John Dunne; Ruben van Hooidonk; James S. Ryan; Cheryl A. Logan (Global Change Biology, 2023)
Projecting the effects of climate change on net reef calcium carbonate production is critical to understanding the future impacts on ecosystem function, but prior estimates have not included corals' natural adaptive capacity to such change. Here we estimate how the ability of symbionts to evolve tolerance to heat stress, or for coral hosts to shuffle to favourable symbionts, and their combination, may influence responses to the combined impacts of ocean warming and acidification under three representative concentration pathway (RCP) emissions scenarios (RCP2.6, RCP4.5 and RCP8.5). We show that symbiont evolution and shuffling, both individually and when combined, favours persistent positive net reef calcium carbonate production. However, our projections of future net calcium carbonate production (NCCP) under climate change vary both spatially and by RCP. For example, 19%–35% of modelled coral reefs are still projected to have net positive NCCP by 2050 if symbionts can evolve increased thermal tolerance, depending on the RCP. Without symbiont adaptive capacity, the number of coral reefs with positive NCCP drops to 9%–13% by 2050. Accounting for both symbiont evolution and shuffling, we project median positive NCPP of coral reefs will still occur under low greenhouse emissions (RCP2.6) in the Indian Ocean, and even under moderate emissions (RCP4.5) in the Pacific Ocean. However, adaptive capacity will be insufficient to halt the transition of coral reefs globally into erosion by 2050 under severe emissions scenarios (RCP8.5).

Macroalgae exhibit diverse responses to human disturbances on coral reefs - Sara E. Cannon; Simon D. Donner; Angela Liu; Pedro C. González Espinosa; Andrew H. Baird; Julia K. Baum; Andrew G. Bauman; Maria Beger; Cassandra E. Benkwitt; Matthew J. Birt; Yannick Chancerelle; Joshua E. Cinner; et al. (Global Change Biology, 2023)
Scientists and managers rely on indicator taxa such as coral and macroalgal cover to evaluate the effects of human disturbance on coral reefs, often assuming a universally positive relationship between local human disturbance and macroalgae. Despite evidence that macroalgae respond to local stressors in diverse ways, there have been few efforts to evaluate relationships between specific macroalgae taxa and local human‐driven disturbance. Using genus‐level monitoring data from 1205 sites in the Indian and Pacific Oceans, we assess whether macroalgae percent cover correlates with local human disturbance while accounting for factors that could obscure or confound relationships. Assessing macroalgae at genus level revealed that no genera were positively correlated with all human disturbance metrics. Instead, we found relationships between the division or genera of algae and specific human disturbances that were not detectable when pooling taxa into a single functional category, which is common to many analyses. The convention to use percent cover of macroalgae as an indication of local human disturbance therefore likely obscures signatures of local anthropogenic threats to reefs. Our limited understanding of relationships between human disturbance, macroalgae taxa, and their responses to human disturbances impedes the ability to diagnose and respond appropriately to these threats.

Evaluation of LiGAPS-Beef to assess extensive pasture-based beef production in three agro-ecological regions in South Africa - Christopher Magona; Abubeker Hassen; Eyob Tesfamariam; Carina Visser; Simon Oosting; A. van der Linden (Livestock Science, 2023)

The effects of feeding dried browse leaves on rumen ammonia levels, methanogens and protozoa amplification of sheep in the Coastal Savannah of Ghana - Felix Owusu Sarkwa; Tsatsu Adogla-Bessa; Othusitse Ricky Madibela; Wanda Nchidzi Mphinyane; Jeremy Simon Perkins; Eric Cofie Timpong-Jones; Amos Nyarko Gyimah; Benjamin Owusu Otu; Christopher Kofi Tudeka (Tropical Animal Health and Production, 2023)

SCAview: an Intuitive Visual Approach to the Integrative Analysis of Clinical Data in Spinocerebellar Ataxias - Mischa Uebachs; Philipp Wegner; Sebastian Schaaf; Simon Kugai; Heike Jacobi; Sheng-Han Kuo; Tetsuo Ashizawa; Juliane Fluck; Sophie Tezenas du Montcel; Peter Bauer; Paola Giunti; Arron Cook; et al. (The Cerebellum, 2023)
With SCAview, we present a prompt and comprehensive tool that enables scientists to browse large datasets of the most common spinocerebellar ataxias intuitively and without technical effort. Basic concept is a visualization of data, with a graphical handling and filtering to select and define subgroups and their comparison. Several plot types to visualize all data points resulting from the selected attributes are provided. The underlying synthetic cohort is based on clinical data from five different European and US longitudinal multicenter cohorts in spinocerebellar ataxia type 1, 2, 3, and 6 (SCA1, 2, 3, and 6) comprising > 1400 patients with overall > 5500 visits. First, we developed a common data model to integrate the clinical, demographic, and characterizing data of each source cohort. Second, the available datasets from each cohort were mapped onto the data model. Third, we created a synthetic cohort based on the cleaned dataset. With SCAview, we demonstrate the feasibility of mapping cohort data from different sources onto a common data model. The resulting browser-based visualization tool with a thoroughly graphical handling of the data offers researchers the unique possibility to visualize relationships and distributions of clinical data, to define subgroups and to further investigate them without any technical effort. Access to SCAview can be requested via the Ataxia Global Initiative and is free of charge.

Production pathways for profitability and valuing ecosystem services for willow coppice in intensive agricultural applications - David Livingstone; Beatrice M. Smyth; Erin Sherry; Simon T. Murray; Aoife M. Foley; Gary A. Lyons; Christopher R. Johnston (Sustainable Production and Consumption, 2023)

Thermodynamic effects drive countergradient responses in the thermal performance of Littorina saxatilis across latitude - Christopher Dwane; Enrico L. Rezende; Oliver Tills; Juan Galindo; Emilio Rolán-Alvarez; Simon Rundle; Manuela Truebano (Science of The Total Environment, 2023)

Sources, pollution, and ecological risk assessment of polycyclic aromatic hydrocarbons (PAHs) in Porto-Novo Lagoon, Benin Republic - Sylvain Zonkpoedjre; Simon Zonkpoedjre; Cajethan Ezeorah; Christopher D. Nwani (Environmental Geochemistry and Health, 2023)

Seafloor Terrain Shapes the Three-dimensional Nursery Value of Mangrove and Seagrass Habitats - Hayden P. Borland; Ben L. Gilby; Christopher J. Henderson; Rod M. Connolly; Bob Gorissen; Nicholas L. Ortodossi; Ashley J. Rummell; Ivan Nagelkerken; Simon J. Pittman; Marcus Sheaves; Andrew D. Olds (Ecosystems, 2023)
Mangroves and seagrasses are important nurseries for many marine species, and this function is linked to the complexity and context of these habitats in coastal seascapes. It is also connected to bathymetric features that influence habitat availability, and the accessibility of refuge habitats, but the significance of terrain variation for nursery function is unknown. To test whether seafloor terrain influences nursery function, we surveyed fish assemblages from mangrove and seagrass habitats in 29 estuaries in eastern Australia with unbaited underwater cameras and quantified the surrounding three-dimensional terrain with a set of complementary surface metrics (that is, depth, aspect, curvature, slope, roughness) applied to sonar-derived bathymetric maps. Terrain metrics explained variability in assemblages in both mangroves and seagrasses, with differing effects for the entire fish assemblage and nursery species composition, and between habitats. Higher depth, plan curvature (concavity or convexity) and roughness (backscatter) were negatively correlated with abundance and diversity in mangroves and positively linked to abundance and diversity in seagrass. Mangrove nursery species (6 species) were most abundant in forests adjacent to flats with concave holes, rough substrates and low-moderate depths, whereas seagrass nursery species (3 species) were most abundant in meadows adjacent to deep channels with soft mounds and ledges. These findings indicate that seafloor terrain influences nursery function and demonstrate contrasting effects of terrain variation in mangroves and seagrass. We suggest that incorporating three-dimensional terrain into coastal conservation and restoration plans could help to improve outcomes for fisheries management, but contrasting strategies might be needed for different nursery habitats.

Planktic foraminifera iodine/calcium ratios from plankton tows - Helge A. Winkelbauer; Babette A. A. Hoogakker; Rosie J. Chance; Catherine V. Davis; Christopher J. Anthony; Juliane Bischoff; Lucy J. Carpenter; Simon R. N. Chenery; Elliott M. Hamilton; Philip Holdship; Victoria L. Peck; Alex J. Poulton; et al. (Frontiers in Marine Science, 2023)
Planktic foraminifera test iodine to calcium ratios represent an emerging proxy method to assess subsurface seawater oxygenation states. Several core-top studies show lower planktic foraminifera I/Ca in locations with oxygen depleted subsurface waters compared to well oxygenated environments. The reasoning behind this trend is that only the oxidized species of iodine, iodate, is incorporated in foraminiferal calcite. The I/Ca of foraminiferal calcite is thought to reflect iodate contents in seawater. To test this hypothesis, we compare planktic foraminifera I/Ca ratios, obtained from plankton tows, with published and new seawater iodate concentrations from 1) the Eastern North Pacific with extensive oxygen depletion, 2) the Benguela Current System with moderately depleted oxygen concentrations, and 3) the well oxygenated North and South Atlantic. We find the lowest I/Ca ratios (0.07 µmol/mol) in planktic foraminifera retrieved from the Eastern North Pacific, and higher values for samples (up to 0.72 µmol/mol) obtained from the Benguela Current System and North and South Atlantic. The I/Ca ratios of plankton tow foraminifera from environments with well oxygenated subsurface waters, however, are an order of magnitude lower compared to core-tops from similarly well-oxygenated regions. This would suggest that planktic foraminifera gain iodine post-mortem, either when sinking through the water column, or during burial.

Edible algae allergenicity – a short report - Christopher A. James; Simon Welham; Peter Rose (Journal of Applied Phycology, 2023)
The use of seaweed and algal derived products in the food industry has grown rapidly in recent times. Major areas of expansion have been in Western countries where algae derived commodities are being utilised as edible foods or sources of high value ingredients. However, studies focused on potential allergenicity attributed to these food items, prevalence of allergenicity, and public health awareness are limited. Therefore, the current research summarises the existing literature focused on algal induced allergy in humans. Of the available literature, a total of 937 titles were identified, and 33 articles underwent subsequent full-text screening. Most research focused on prevalence and were derived from studies conducted in Europe (58%), North America and Canada (33%), and the remainder Australia and South Korea (9%). No studies addressed the need for public education or labelling of algal products. Our review reports that the available evidence identified points to algal derived products as being potential sources of allergens in the human food chain. Several components have been characterised that are shown to induce allergic responses in humans. Few studies have assessed the prevalence of algal allergenicity in the general population and as such further research is warranted given the increased usage of these products in the food industry.

A spatially explicit approach to assessing commodity-driven fertilizer use and its impact on biodiversity - Karin Eliasson; Christopher D. West; Simon A. Croft; Jonathan M.H. Green (Journal of Cleaner Production, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Understanding the potential release of microplastics from coatings used on commercial ships - Mario N. Tamburri; Zhi Yang Soon; Christopher Scianni; Christer L. Øpstad; Neil S. Oxtoby; Simon Doran; Lisa A. Drake (Frontiers in Marine Science, 2022)
Microplastic pollution in the ocean is a critical, global environmental concern. Although believed to be a comparatively small contributor, the paints applied to commercial ships have been identified as a source of microplastics because polymers are used as binding agents in all anticorrosive and antifouling marine coatings. Furthermore, the release of microplastics from coatings may be amplified by in-water cleaning operations to remove biofouling. A comprehensive, detailed assessment and review of the array of commercial ships’ coatings, specifically characteristics, behavior, and fate over time, has not been conducted in the context of ocean microplastic pollution. This Policy Brief identifies gaps and proposes actions to better understand the fate of released particles with the goal to inform appropriate and effective solutions.

Paleoenvironments and hydrocarbon reservoir potentials from the selected sedimentary basins in Nigeria using sedimentary facies and textural analyses - Godwin Okumagbe Aigbadon; Azuka Ocheli; Obinna Chigoziem Akakuru; Ernest Orji Akudo; Simon Dalom Christopher; Ogaga Esharive; Joseph Amobi Francis (Journal of Sedimentary Environments, 2022)

Assessment of Polycyclic Aromatic Hydrocarbons in Water and Fish and the Associated Human Health Risk at Porto-Novo Lagoon, Benin Republic - Sylvain Zonkpoedjre; Simon Zonkpoedjre; Gerald Nnamdi Attamah; Christopher D. Nwani (Water, Air, & Soil Pollution, 2022)

Evaluating expert‐based habitat suitability information of terrestrial mammals with GPS‐ tracking data - Maarten J. E. Broekman; Jelle P. Hilbers; Mark A. J. Huijbregts; Thomas Mueller; Abdullahi H. Ali; Henrik Andrén; Jeanne Altmann; Malin Aronsson; Nina Attias; Hattie L. A. Bartlam‐Brooks; Floris M. van Beest; Jerrold L. Belant; et al. (Global Ecology and Biogeography, 2022)
Aim Macroecological studies that require habitat suitability data for many species often derive this information from expert opinion. However, expert‐based information is inherently subjective and thus prone to errors. The increasing availability of GPS tracking data offers opportunities to evaluate and supplement expert‐based information with detailed empirical evidence. Here, we compared expert‐based habitat suitability information from the International Union for Conservation of Nature (IUCN) with habitat suitability information derived from GPS‐tracking data of 1,498 individuals from 49 mammal species. Location Worldwide. Time period 1998–2021. Major taxa studied Forty‐nine terrestrial mammal species. Methods Using GPS data, we estimated two measures of habitat suitability for each individual animal: proportional habitat use (proportion of GPS locations within a habitat type), and selection ratio (habitat use relative to its availability). For each individual we then evaluated whether the GPS‐based habitat suitability measures were in agreement with the IUCN data. To that end, we calculated the probability that the ranking of empirical habitat suitability measures was in agreement with IUCN's classification into suitable, marginal and unsuitable habitat types. Results IUCN habitat suitability data were in accordance with the GPS data (> 95% probability of agreement) for 33 out of 49 species based on proportional habitat use estimates and for 25 out of 49 species based on selection ratios. In addition, 37 and 34 species had a > 50% probability of agreement based on proportional habitat use and selection ratios, respectively. Main conclusions We show how GPS‐tracking data can be used to evaluate IUCN habitat suitability data. Our findings indicate that for the majority of species included in this study, it is appropriate to use IUCN habitat suitability data in macroecological studies. Furthermore, we show that GPS‐tracking data can be used to identify and prioritize species and habitat types for re‐evaluation of IUCN habitat suitability data.

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Drivers and physical processes of drought events over the State of São Paulo, Brazil - Abayomi A. Abatan; Simon F. B. Tett; Buwen Dong; Christopher Cunningham; Conrado M. Rudorff; Nicholas P. Klingaman; Rafael C. de Abreu (Climate Dynamics, 2022)
The State of São Paulo, Brazil (SSP) was impacted by severe water shortages during the intense austral summer drought of 2013/2014 and 2014/2015 (1415SD). This study seeks to understand the features and physical processes associated with these summer droughts in the context of other droughts over the region during 1961–2010. Thus, this study examines the spatio-temporal characteristics of anomalously low precipitation over SSP and the associated large-scale dynamics at seasonal timescales, using an observation-based dataset from the Climatic Research Unit (CRU) and model simulation outputs from the Met Office Hadley Centre Global Environment Model (HadGEM3-GA6 at N216 resolution). The study analyzes Historical and Natural simulations from the model to examine the role of human-induced climate forcing on droughts over SSP. Composites of large-scale fields associated with droughts are derived from ERA-20C and ERA-Interim reanalysis and the model simulations. HadGEM3-GA6 simulations capture the observed interannual variability of normalized precipitation anomalies over SSP, but with biases. Drought events over SSP are related to subsidence over the region. This is associated with reduced atmospheric moisture over the region as indicated by the analysis of the vertically integrated moisture flux convergence, which is dominated by reduced moisture flux convergence. The Historical simulations simulate the subsidence associated with droughts, but there are magnitude and location biases. The similarities between the circulation features of the severe 1415SD and other drought events over the region show that understanding of the dynamics of the past drought events over SSP could guide assessment of changes in risk of future droughts and improvements of model performance. The study highlights the merits and limitations of the HadGEM3-GA6 simulations. The model possesses the skills in simulating the large-scale atmospheric circulations modulating precipitation variability, leading to drought conditions over SSP.

Changes in tree drought sensitivity provided early warning signals to the California drought and forest mortality event - Rachel M. Keen; Steven L. Voelker; S.‐Y. Simon Wang; Barbara J. Bentz; Michael L. Goulden; Cody R. Dangerfield; Charlotte C. Reed; Sharon M. Hood; Adam Z. Csank; Todd E. Dawson; Andrew G. Merschel; Christopher J. Still (Global Change Biology, 2022)
Climate warming in recent decades has negatively impacted forest health in the western United States. Here, we report on potential early warning signals (EWS) for drought‐related mortality derived from measurements of tree‐ring growth (ring width index; RWI) and carbon isotope discrimination (∆ 13 C), primarily focused on ponderosa pine ( Pinus ponderosa ). Sampling was conducted in the southern Sierra Nevada Mountains, near the epicenter of drought severity and mortality associated with the 2012–2015 California drought and concurrent outbreak of western pine beetle ( Dendroctonus brevicomis ). At this site, we found that widespread mortality was presaged by five decades of increasing sensitivity (i.e., increased explained variation) of both tree growth and ∆ 13 C to Palmer Drought Severity Index (PDSI). We hypothesized that increasing sensitivity of tree growth and ∆ 13 C to hydroclimate constitute EWS that indicate an increased likelihood of widespread forest mortality caused by direct and indirect effects of drought. We then tested these EWS in additional ponderosa pine‐dominated forests that experienced varying mortality rates associated with the same California drought event. In general, drier sites showed increasing sensitivity of RWI to PDSI over the last century, as well as higher mortality following the California drought event compared to wetter sites. Two sites displayed evidence that thinning or fire events that reduced stand basal area effectively reversed the trend of increasing hydroclimate sensitivity. These comparisons indicate that reducing competition for soil water and/or decreasing bark beetle host tree density via forest management—particularly in drier regions—may buffer these forests against drought stress and associated mortality risk. EWS such as these could provide land managers more time to mitigate the extent or severity of forest mortality in advance of droughts. Substantial efforts at deploying additional dendrochronological research in concert with remote sensing and forest modeling will aid in forecasting of forest responses to continued climate warming.

Targeting Tau Mitigates Mitochondrial Fragmentation and Oxidative Stress in Amyotrophic Lateral Sclerosis - Tiziana Petrozziello; Evan A. Bordt; Alexandra N. Mills; Spencer E. Kim; Ellen Sapp; Benjamin A. Devlin; Abigail A. Obeng-Marnu; Sali M. K. Farhan; Ana C. Amaral; Simon Dujardin; Patrick M. Dooley; Christopher Henstridge; et al. (Molecular Neurobiology, 2022)

Decline in Atlantic wolffish Anarhichas lupus in the North Sea : Impacts of fishing pressure and climate change - Joanna K. Bluemel; Simon H. Fischer; David W. Kulka; Christopher P. Lynam; Jim R. Ellis (Journal of Fish Biology, 2022)
Anarhichas lupus is a boreo‐Arctic species with biological characteristics often associated with vulnerability to overexploitation. Although not commercially targeted in the North Sea, A. lupus is a bycatch species in mixed demersal fisheries. Here we provide an overview of the status of A. lupus in the North Sea, as observed from commercial landings and fishery‐independent trawl survey data. A. lupus was once common across much of the central and northern North Sea but, since the 1980s, have declined in abundance, demographic characteristics (reduced size) and geographical range, with the shallower and more southerly parts of its range most impacted. A. lupus is still relatively frequent in the northern North Sea, where fishing intensity, though decreasing, is high. Bycatch through fishing remains a potential threat and, considering the likely impacts of predicted climate change on cold‐water species, risks of further regional depletion and/or range contraction remain. Whether or not A. lupus is able to re‐establish viable populations in former habitat in UK coastal waters is unknown. Given the lack of data, the precautionary principle would suggest that manageable pressures be minimized where the species and its habitat are at risk of further impacts, and more regular assessments of population status be undertaken.

The aquaponic principle—It is all about coupling - Gösta F. M. Baganz; Ranka Junge; Maria C. Portella; Simon Goddek; Karel J. Keesman; Daniela Baganz; Georg Staaks; Christopher Shaw; Frank Lohrberg; Werner Kloas (Reviews in Aquaculture, 2022)
The aquaponic principle is the coupling of animal aquaculture (e.g. fish) with plant production (e.g. vegetables) for saving resources. At present, various definitions of aquaponics exist, some bearing the risk of misinterpretation by dismissing the original meaning or being contradictory. In addition, there is no standard terminology for the aspects of coupling between the aquaponic subsystems. In this study, we addressed both issues. (1) We developed new or revised definitions that are summarised by: Aquaponic farming comprises aquaponics (which couples tank‐based animal aquaculture with hydroponics) and trans‐aquaponics, which extends aquaponics to tankless aquaculture as well as non‐hydroponics plant cultivation methods. Within our conceptual system, the term aquaponics corresponds to the definitions of FAO and EU. (2) A system analysis approach was utilised to explore different aquaponic setups aiming to better describe the way aquaponic subsystems are connected. We introduced the new terms ‘coupling type’ and ‘coupling degree’, where the former qualitatively characterises the water‐mediated connections of aquaponic subsystems. A system with on‐demand nutrient water supply for the independent operating plant cultivation is an ‘on‐demand coupled system’ and we propose to deprecate the counterintuitive term ‘decoupled system’ for this coupling type. The coupling degree comprises a set of parameters to quantitatively determine the coupling's efficiency of internal streams, for example, water and nutrients. This new framework forms a basis for improved communication, provides a uniform metric for comparing aquaponic facilities, and offers criteria for facility optimisation. In future system descriptions, it will simplify evaluation of the coupling's contribution to sustainability of aquaponics.

Ambrein: a minor, but common constituent of mammalian faeces? - Steven J. Rowland; Paul A. Sutton; Barbara von der Lühe; John K. Volkman; Christopher H. Vane; Simon N. Ingram; Charlotte Dunn; Diane Claridge (Natural Product Research, 2021)

Wealth and urbanization shape medium and large terrestrial mammal communities - Seth B. Magle; Mason Fidino; Heather A. Sander; Adam T. Rohnke; Kelli L. Larson; Travis Gallo; Cria A. M. Kay; Elizabeth W. Lehrer; Maureen H. Murray; Solny A. Adalsteinsson; Adam A. Ahlers; Whitney J. B. Anthonysamy; et al. (Global Change Biology, 2021)
Urban biodiversity provides critical ecosystem services and is a key component to environmentally and socially sustainable cities. However, biodiversity varies greatly within and among cities, leading to human communities with changing and unequal experiences with nature. The “luxury effect,” a hypothesis that predicts a positive correlation between wealth, typically measured by per capita income, and species richness may be one indication of these inequities. While the luxury effect is well studied for some taxa, it has rarely been investigated for mammals, which provide unique ecosystem services (e.g., biological pest control) and exhibit significant potential for negative human–wildlife interactions (e.g., nuisances or conflicts). We analyzed a large dataset of mammal detections across 20 North American cities to test whether the luxury effect is consistent for medium‐ to large‐sized terrestrial mammals across diverse urban contexts. Overall, support for the luxury effect, as indicated by per capita income, was inconsistent; we found evidence of a luxury effect in approximately half of our study cities. Species richness was, however, highly and negatively correlated with urban intensity in most cities. We thus suggest that economic factors play an important role in shaping urban mammal communities for some cities and species, but that the strongest driver of urban mammal diversity is urban intensity. To better understand the complexity of urban ecosystems, ecologists and social scientists must consider the social and political factors that drive inequitable human experiences with nature in cities.

The influence of seafloor terrain on fish and fisheries: A global synthesis - Hayden P. Borland; Ben L. Gilby; Christopher J. Henderson; Javier X. Leon; Thomas A. Schlacher; Rod M. Connolly; Simon J. Pittman; Marcus Sheaves; Andrew D. Olds (Fish and Fisheries, 2021)
The structure of seafloor terrain affects the distribution and diversity of animals in all seascapes. Effects of terrain on fish assemblages have been reported from most ecosystems, but it is unclear whether bathymetric effects vary among seascapes or change in response to seafloor modification by humans. We reviewed the global literature linking seafloor terrain to fish species and assemblages (96 studies) and determined that relief (e.g. depth), complexity (e.g. roughness), feature classes (e.g. substrate types) and morphology (e.g. curvature), have widespread effects on fish assemblages. Research on the ecological consequences of terrain have focused on coral reefs, rocky reefs, continental shelves and the deep sea ( n ≥ 20 studies), but are rarely tested in estuaries ( n = 7). Fish associate with a variety of terrain attributes, and assemblages change with variation in the depth and aspect of bathymetric features in reef and shelf seascapes, and in the deep sea. Fish from different seascapes also respond to distinct metrics, with fluctuations in slope of slope (coral reefs), rugosity (rocky reefs) and slope (continental shelves, deep sea) each linked to changes in assemblage composition. Terrain simplification from coastal urbanization (e.g. dredging) and resource extraction (e.g. trawling) can reduce fish diversity and abundance, but assemblages can also recover inside effective marine reserves. The consequences of these terrain changes for fish and fisheries are, however, rarely measured in most seascapes. The key challenge now is to examine how terrain modification and conservation combine to alter fish distributions and fisheries productivity across diverse coastal seascapes.

Disruption of duplicated yellow genes in Bactrocera tryoni modifies pigmentation colouration and impacts behaviour - Thu N. M. Nguyen; Vivian Mendez; Christopher Ward; Peter Crisp; Alexie Papanicolaou; Amanda Choo; Phillip W. Taylor; Simon W. Baxter (Journal of Pest Science, 2021)

Paternal leakage inheritance and a fitness cost are associated with the chloroplastic psbA gene controlled metribuzin tolerance in lentil (Lens culinaris) - Larn S. McMurray; Christopher Preston; Albert Vandenberg; Isabel Munoz-Santa; Dili Mao; Kirstin E. Bett; Simon Michelmore; Jeffrey G. Paull (Euphytica, 2021)

Reintroducing extirpated herbivores could partially reverse the late Quaternary decline of large and grazing species - Simon D. Schowanek; Matt Davis; Erick J. Lundgren; Owen Middleton; John Rowan; Rasmus Ø. Pedersen; Daniel Ramp; Christopher J. Sandom; Jens‐Christian Svenning (Global Ecology and Biogeography, 2021)
Aim Reinstating large, native herbivores is an essential component of ecological restoration efforts, as these taxa can be important drivers of ecological processes. However, many herbivore species have gone globally or regionally extinct during the last 50,000 years, leaving simplified herbivore assemblages and trophically downgraded ecosystems. Here, we discuss to what extent trophic rewilding can undo these changes by reinstating native herbivores. Location Global. Time period We report functional trait changes from the Late Pleistocene to the present, and estimated trait changes under future scenarios. Major taxa studied Wild, large (≥ 10 kg), terrestrial, mammalian herbivores. Methods We use a functional trait dataset containing all late Quaternary large herbivores ≥ 10 kg to look at changes in the body mass and diet composition of herbivore assemblages, a proxy for species’ ecological effects. First, we assess how these traits have changed from the Late Pleistocene to the present. Next, we quantify how the current body mass and diet composition would change if all extant, wild herbivores were restored to their native ranges (and if no functional replacements were used), exploring scenarios with different baselines. Results Defaunation has primarily removed large and grazing herbivores. Reinstating extant herbivores across their native ranges would reverse these changes, especially when reinstating them to their prehistoric distributions. It would partially restore herbivore body mass and diet composition to pre‐anthropogenic conditions. However, in the absence of complementary interventions (e.g., introducing functional replacements), many herbivore assemblages would remain down‐sized and browser dominated, relative to pre‐anthropogenic conditions. Main conclusions Many terrestrial herbivore assemblages—and hence ecosystems—would remain trophically downgraded, even after bringing back all extant, native herbivores. Therefore, complementary interventions would be required to achieve complete functional restoration. Nevertheless, our findings suggest that reintroducing the remaining native herbivores would diversify the herbivory and disturbances of herbivore assemblages.

Simple larvae sustain the world’s smallest marine vertebrates - Christopher H. R. Goatley; Simon J. Brandl; Stephen Wroe; David R. Bellwood (Coral Reefs, 2021)

A juvenile Tristan albatross (Diomedea dabbenena) on land at the Crozet Islands - Alexander L. Bond; Christopher Taylor; David Kinchin-Smith; Derren Fox; Emma Witcutt; Peter G. Ryan; Simon P. Loader; Henri Weimerskirch (Polar Biology, 2021)
Albatrosses and other seabirds are generally highly philopatric, returning to natal colonies when they achieve breeding age. This is not universal, however, and cases of extraordinary vagrancy are rare. The Tristan Albatross ( Diomedea dabbenena ) breeds on Gough Island in the South Atlantic Ocean, with a small population on Inaccessible Island, Tristan da Cunha, ca 380 km away. In 2015, we observed an adult male albatross in Gonydale, Gough Island, which had been ringed on Ile de la Possession, Crozet Islands in 2009 when it was assumed to be an immature Wandering Albatross ( D. exulans ). We sequenced 1109 bp of the cytochrome b mitochondrial gene from this bird, and confirmed it to be a Tristan Albatross, meaning its presence on Crozet 6 years previous, and nearly 5000 km away, was a case of prospecting behaviour in a heterospecific colony. Given the challenges in identifying immature Diomedea albatrosses, such dispersal events may be more common than thought previously.

Rapid evolutionary changes in gene expression in response to climate fluctuations - Elena Hamann; Christopher S. Pauli; Zoé Joly‐Lopez; Simon C. Groen; Joshua S. Rest; Nolan C. Kane; Michael D. Purugganan; Steven J. Franks (Molecular Ecology, 2021)
There is now abundant evidence of rapid evolution in natural populations, but the genetic mechanisms of these changes remain unclear. One possible route to rapid evolution is through changes in the expression of genes that influence traits under selection. We examined contemporary evolutionary gene expression changes in plant populations responding to environmental fluctuations. We compared genome‐wide gene expression, using RNA‐seq, in two populations of Brassica rapa collected over four time points between 1997 and 2014, during which precipitation in southern California fluctuated dramatically and phenotypic and genotypic changes occurred. By combining transcriptome profiling with the resurrection approach, we directly examined evolutionary changes in gene expression over time. For both populations, we found a substantial number of differentially expressed genes between generations, indicating rapid evolution in the expression of many genes. Using existing gene annotations, we found that many changes occurred in genes involved in regulating stress responses and flowering time. These appeared related to the fluctuations in precipitation and were potentially adaptive. However, the evolutionary changes in gene expression differed across generations within and between populations, indicating largely independent evolutionary trajectories across populations and over time. Our study provides strong evidence for rapid evolution in gene expression, and indicates that changes in gene expression can be one mechanism of rapid evolutionary responses to selection episodes. This study also illustrates that combining resurrection studies with transcriptomics is a powerful approach for investigating evolutionary changes at the gene regulatory level, and will provide new insights into the genetic basis of contemporary evolution.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Climate change, crops and commodity traders: subnational trade analysis highlights differentiated risk exposure - Emilie Stokeld; Simon A. Croft; Jonathan M. H. Green; Christopher D. West (Climatic Change, 2020)
The global food system is increasingly interconnected and under pressure to support growing demand. At the same time, crop production is facing new and uncertain impacts from climate change. To date, understanding how downstream supply chain actors, such as commodity traders, are exposed to climate change risks has been difficult due to a lack of high-resolution climate and trade data. However, the recent availability of supply chain data linking subnational production to downstream actors, and gridded projections of crop yield under climate change, allows us to assess individual commodity trader exposure to long-term climate change risk. We apply such an analysis to soy production in Brazil, the world’s largest soy exporter. Whilst uncertainty across crop models’ yield projections means it remains difficult to accurately predict how production across the region will be affected by climate change, we demonstrate that the risk exposure of trading actors differs substantially due to the heterogeneity in their sourcing. Our study offers a first attempt to analyze subnational climate risk to individual trading actors operating across an entire production landscape, leading to more precise risk exposure analysis. With sufficient subnational data, this method can be applied to any crop and country combination, and in the context of wider food security issues, it will be pertinent to apply these methods across other production systems and downstream actors in the food system.

Characterizing Exposure to and Sharing Knowledge of Drivers of Environmental Change in the St. Lawrence System in Canada - David Beauchesne; Rémi M. Daigle; Steve Vissault; Dominique Gravel; Andréane Bastien; Simon Bélanger; Pascal Bernatchez; Marjolaine Blais; Hugo Bourdages; Clément Chion; Peter S. Galbraith; Benjamin S. Halpern; et al. (Frontiers in Marine Science, 2020)

Increased yield and CO 2 sequestration potential with the C 4 cereal Sorghum bicolor cultivated in basaltic rock dust‐amended agricultural soil - Mike E. Kelland; Peter W. Wade; Amy L. Lewis; Lyla L. Taylor; Binoy Sarkar; M. Grace Andrews; Mark R. Lomas; T. E. Anne Cotton; Simon J. Kemp; Rachael H. James; Christopher R. Pearce; Sue E. Hartley; et al. (Global Change Biology, 2020)
Land‐based enhanced rock weathering (ERW) is a biogeochemical carbon dioxide removal (CDR) strategy aiming to accelerate natural geological processes of carbon sequestration through application of crushed silicate rocks, such as basalt, to croplands and forested landscapes. However, the efficacy of the approach when undertaken with basalt, and its potential co‐benefits for agriculture, require experimental and field evaluation. Here we report that amending a UK clay‐loam agricultural soil with a high loading (10 kg/m 2 ) of relatively coarse‐grained crushed basalt significantly increased the yield (21 ± 9.4%, SE ) of the important C 4 cereal Sorghum bicolor under controlled environmental conditions, without accumulation of potentially toxic trace elements in the seeds. Yield increases resulted from the basalt treatment after 120 days without P‐ and K‐fertilizer addition. Shoot silicon concentrations also increased significantly (26 ± 5.4%, SE ), with potential benefits for crop resistance to biotic and abiotic stress. Elemental budgets indicate substantial release of base cations important for inorganic carbon removal and their accumulation mainly in the soil exchangeable pools. Geochemical reactive transport modelling, constrained by elemental budgets, indicated CO 2 sequestration rates of 2–4 t CO 2 /ha, 1–5 years after a single application of basaltic rock dust, including via newly formed soil carbonate minerals whose long‐term fate requires assessment through field trials. This represents an approximately fourfold increase in carbon capture compared to control plant–soil systems without basalt. Our results build support for ERW deployment as a CDR technique compatible with spreading basalt powder on acidic loamy soils common across millions of hectares of western European and North American agriculture.

Opportunities for agent‐based modelling in human dimensions of fisheries - Matthew G. Burgess; Ernesto Carrella; Michael Drexler; Robert L. Axtell; Richard M. Bailey; James R. Watson; Reniel B. Cabral; Michaela Clemence; Christopher Costello; Chris Dorsett; Steven D. Gaines; Emily S. Klein; et al. (Fish and Fisheries, 2020)
Models of human dimensions of fisheries are important to understanding and predicting how fishing industries respond to changes in marine ecosystems and management institutions. Advances in computation have made it possible to construct agent‐based models (ABMs)—which explicitly describe the behaviour of individual people, firms or vessels in order to understand and predict their aggregate behaviours. ABMs are widely used for both academic and applied purposes in many settings including finance, urban planning and the military, but are not yet mainstream in fisheries science and management, despite a growing literature. ABMs are well suited to understanding emergent consequences of fisher interactions, heterogeneity and bounded rationality, especially in complex ecological, social and institutional contexts. For these reasons, we argue that ABMs of human behaviour can contribute significantly to human dimensions of fisheries in three areas: (a) understanding interactions between multiple management institutions; (b) incorporating cognitive and behavioural sciences into fisheries science and practice; and (c) understanding and projecting the social consequences of management institutions. We provide simple examples illustrating the potential for ABMs in each of these areas, using conceptual (“toy”) versions of the POSEIDON model. We argue that salient strategic advances in these areas could pave the way for increased tactical use of ABMs in fishery management settings. We review common ABM development and application challenges, with the aim of providing guidance to beginning ABM developers and users studying human dimensions of fisheries.

Dietary and habitat niche partitioning in congeneric cryptobenthic reef fish species - Simon J. Brandl; Jordan M. Casey; Christopher P. Meyer (Coral Reefs, 2020)

Invasive non‐native species likely to threaten biodiversity and ecosystems in the Antarctic Peninsula region - Kevin A. Hughes; Oliver L. Pescott; Jodey Peyton; Tim Adriaens; Elizabeth J. Cottier‐Cook; Gillian Key; Wolfgang Rabitsch; Elena Tricarico; David K. A. Barnes; Naomi Baxter; Mark Belchier; Denise Blake; et al. (Global Change Biology, 2020)
The Antarctic is considered to be a pristine environment relative to other regions of the Earth, but it is increasingly vulnerable to invasions by marine, freshwater and terrestrial non‐native species. The Antarctic Peninsula region (APR), which encompasses the Antarctic Peninsula, South Shetland Islands and South Orkney Islands, is by far the most invaded part of the Antarctica continent. The risk of introduction of invasive non‐native species to the APR is likely to increase with predicted increases in the intensity, diversity and distribution of human activities. Parties that are signatories to the Antarctic Treaty have called for regional assessments of non‐native species risk. In response, taxonomic and Antarctic experts undertook a horizon scanning exercise using expert opinion and consensus approaches to identify the species that are likely to present the highest risk to biodiversity and ecosystems within the APR over the next 10 years. One hundred and three species, currently absent in the APR, were identified as relevant for review, with 13 species identified as presenting a high risk of invading the APR. Marine invertebrates dominated the list of highest risk species, with flowering plants and terrestrial invertebrates also represented; however, vertebrate species were thought unlikely to establish in the APR within the 10 year timeframe. We recommend (a) the further development and application of biosecurity measures by all stakeholders active in the APR, including surveillance for species such as those identified during this horizon scanning exercise, and (b) use of this methodology across the other regions of Antarctica. Without the application of appropriate biosecurity measures, rates of introductions and invasions within the APR are likely to increase, resulting in negative consequences for the biodiversity of the whole continent, as introduced species establish and spread further due to climate change and increasing human activity.

Feeding Whole Thraustochytrid Biomass to Cultured Atlantic Salmon (Salmo salar) Fingerlings: Culture Performance and Fatty Acid Incorporation - Kim Jye Lee Chang; Christopher C. Parrish; Cedric J. Simon; Andrew T. Revill; Peter D. Nichols (Journal of Marine Science and Engineering, 2020)
Replacement of fish oil by 5% thraustochytrid whole cell biomass in diets for Atlantic salmon had no ill effect on fish growth performance, carcass total lipid and total fatty acid content. Carcass fatty acid composition indicated incorporation of the dietary thraustochytrid-derived fatty acids. This was confirmed by compound specific stable isotope analysis (CSIA) which revealed significantly 13C-depleted (δ13C value of −24‰) ω3 long-chain (≥C20) polyunsaturated fatty acids (ω3 LC-PUFAs) in the fingerlings fed the thraustochytrid biomass containing diet, reflecting the highly 13C-depleted glycerol used to grow the thraustochytrid cultures. This finding demonstrates the bioavailability of the ω3 LC-PUFA of the Australian strain thraustochytrid culture (TC) 20 from the whole cell biomass that was partly cultivated on crude glycerol produced during biodiesel manufacturing. This paper demonstrates the value of Australian thraustochytrid strains grown heterotrophically for their wider biotechnological potential including as a source of higher value lipids, in particular the health-benefitting ω3 LC-PUFA, for use in aquaculture and other applications.

Yield reduction historically associated with the Aegilops ventricosa 7DV introgression is genetically and physically distinct from the eyespot resistance gene Pch1 - Marianna Pasquariello; Simon Berry; Christopher Burt; Cristobal Uauy; Paul Nicholson (Theoretical and Applied Genetics, 2020)
Key message Yield penalty and increased grain protein content traits associated with Aegilops ventricosa 7D introgression have been mapped for the first time, and they are physically distinct from the eyespot resistance locus Pch1. Abstract Wheat wild relatives represent an important source of genetic variation, but introgression of agronomically relevant genes, such as for disease resistance, may lead to the simultaneous introduction of genetically linked deleterious traits. Pch1 is a dominant gene, conferring resistance to eyespot and was introgressed to wheat from Aegilops ventricosa as part of a large segment of the 7D V chromosome. This introgression has been associated with a significant yield reduction and a concomitant increase in grain protein content. In this study, we evaluated both traits and their relationship to the location of the Pch1 gene. We found that both QTLs were clearly distinct from the Pch1 gene, being located on a different linkage group to Pch1 . In addition, we found that the QTL for increased grain protein content was strong and consistent across field trials, whereas the yield penalty QTL was unstable and environmentally dependent. The yield and grain protein content QTLs were genetically linked and located in the same linkage group. This finding is due in part to the small size of the population, and to the restricted recombination between wheat 7D and Ae. ventricosa 7D v chromosomes. Although recombination in this interval is rare, it does occur. A recombinant line containing Pch1 and 7D_KASP6 , the marker associated with increase in grain protein content, but not Xwmc221 , the marker associated with the yield penalty effect, was identified.

Integrative concepts and practices of health in transdisciplinary social ecology - Timo Assmuth; Xianwen Chen; Christopher Degeling; Tari Haahtela; Katherine N. Irvine; Hans Keune; Richard Kock; Salla Rantala; Simon Rüegg; Suvi Vikström (Socio-Ecological Practice Research, 2020)
Increasing recognition of interdependencies of the health of humans, other organisms and ecosystems, and of their importance to socio-ecological systems, necessitates application of integrative concepts such as One Health and EcoHealth. These concepts open new perspectives for research and practice but also generate confusion and divergent opinion, prompting new theories, and call for empirical clarification and evaluation. Through a semi-systematic evaluation of knowledge generation in scientific publications (comprised of literature reviews, conceptual models and analyses of communities of practice), we show how integrative concepts and approaches to health evolve and are adopted. Our findings indicate that while their contexts, goals and rationales vary, integrative concepts of health essentially arise from shared interests in living systems. Despite recent increased attention to ecological and societal aspects of health including broader sustainability issues, the focus remains anthropocentric and oriented towards biomedicine. Practices reflect and in turn transform these concepts, which together with practices also influence ways of integration. Overarching narratives vary between optimism and pessimism towards integrated health and knowledge. We conclude that there is an urgent need for better, coherent and more deeply integrative health concepts, approaches and practices to foster the well-being of humans, other animals and ecosystems. Consideration of these concepts and practices has methodological and political importance, as it will transform thinking and action on both society and nature and specifically can enrich science and practice, expanding their scope and linking them better. Transdisciplinary efforts are crucial to developing such concepts and practices to properly address the multiple facets of health and to achieve their appropriate integration for the socio-ecological systems at stake. We propose the term “transdisciplinary health” to denote the new approaches needed.

Development of a neural rosette formation assay (RoFA) to identify neurodevelopmental toxicants and to characterize their transcriptome disturbances - Nadine Dreser; Katrin Madjar; Anna-Katharina Holzer; Marion Kapitza; Christopher Scholz; Petra Kranaster; Simon Gutbier; Stefanie Klima; David Kolb; Christian Dietz; Timo Trefzer; Johannes Meisig; et al. (Archives of Toxicology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Quantifying trends and uncertainty in prehistoric forest composition in the upper Midwestern United States - Andria Dawson; Christopher J. Paciorek; Simon J. Goring; Stephen T. Jackson; Jason S. McLachlan; John W. Williams (Ecology, 2019)
Forest ecosystems in eastern North America have been in flux for the last several thousand years, well before Euro‐American land clearance and the 20th‐century onset of anthropogenic climate change. However, the magnitude and uncertainty of prehistoric vegetation change have been difficult to quantify because of the multiple ecological, dispersal, and sedimentary processes that govern the relationship between forest composition and fossil pollen assemblages. Here we extend STEPPS, a Bayesian hierarchical spatiotemporal pollen–vegetation model, to estimate changes in forest composition in the upper Midwestern United States from about 2,100 to 300 yr ago. Using this approach, we find evidence for large changes in the relative abundance of some species, and significant changes in community composition. However, these changes took place against a regional background of changes that were small in magnitude or not statistically significant, suggesting complexity in the spatiotemporal patterns of forest dynamics. The single largest change is the infilling of Tsuga canadensis in northern Wisconsin over the past 2,000 yr. Despite range infilling, the range limit of T. canadensis was largely stable, with modest expansion westward. The regional ecotone between temperate hardwood forests and northern mixed hardwood/conifer forests shifted southwestward by 15–20 km in Minnesota and northwestern Wisconsin. Fraxinus , Ulmus , and other mesic hardwoods expanded in the Big Woods region of southern Minnesota. The increasing density of paleoecological data networks and advances in statistical modeling approaches now enables the confident detection of subtle but significant changes in forest composition over the last 2,000 yr.

Estimating aboveground net biomass change for tropical and subtropical forests: Refinement of IPCC default rates using forest plot data - Daniela Requena Suarez; Danaë M. A. Rozendaal; Veronique De Sy; Oliver L. Phillips; Esteban Alvarez‐Dávila; Kristina Anderson‐Teixeira; Alejandro Araujo‐Murakami; Luzmila Arroyo; Timothy R. Baker; Frans Bongers; Roel J. W. Brienen; Sarah Carter; et al. (Global Change Biology, 2019)
As countries advance in greenhouse gas (GHG) accounting for climate change mitigation, consistent estimates of aboveground net biomass change (∆AGB) are needed. Countries with limited forest monitoring capabilities in the tropics and subtropics rely on IPCC 2006 default ∆AGB rates, which are values per ecological zone, per continent. Similarly, research into forest biomass change at a large scale also makes use of these rates. IPCC 2006 default rates come from a handful of studies, provide no uncertainty indications and do not distinguish between older secondary forests and old‐growth forests. As part of the 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories, we incorporate ∆AGB data available from 2006 onwards, comprising 176 chronosequences in secondary forests and 536 permanent plots in old‐growth and managed/logged forests located in 42 countries in Africa, North and South America and Asia. We generated ∆AGB rate estimates for younger secondary forests (≤20 years), older secondary forests (>20 years and up to 100 years) and old‐growth forests, and accounted for uncertainties in our estimates. In tropical rainforests, for which data availability was the highest, our ∆AGB rate estimates ranged from 3.4 (Asia) to 7.6 (Africa) Mg ha −1 year −1 in younger secondary forests, from 2.3 (North and South America) to 3.5 (Africa) Mg ha −1 year −1 in older secondary forests, and 0.7 (Asia) to 1.3 (Africa) Mg ha −1 year −1 in old‐growth forests. We provide a rigorous and traceable refinement of the IPCC 2006 default rates in tropical and subtropical ecological zones, and identify which areas require more research on ∆AGB. In this respect, this study should be considered as an important step towards quantifying the role of tropical and subtropical forests as carbon sinks with higher accuracy; our new rates can be used for large‐scale GHG accounting by governmental bodies, nongovernmental organizations and in scientific research.

Island questions: the chronology of the Brochtorff Circle at Xagħra, Gozo, and its significance for the Neolithic sequence on Malta - Caroline Malone; Nathaniel Cutajar; T. Rowan McLaughlin; Bernardette Mercieca-Spiteri; Anthony Pace; Ronika K. Power; Simon Stoddart; Sharon Sultana; Christopher Bronk Ramsey; Elaine Dunbar; Alex Bayliss; Frances Healy; et al. (Archaeological and Anthropological Sciences, 2019)

Constraining Southern Ocean Air-Sea-Ice Fluxes Through Enhanced Observations - Sebastiaan Swart; Sarah T. Gille; Bruno Delille; Simon Josey; Matthew Mazloff; Louise Newman; Andrew F. Thompson; Jim Thomson; Brian Ward; Marcel D. du Plessis; Elizabeth C. Kent; James Girton; et al. (Frontiers in Marine Science, 2019)

Twenty-three unsolved problems in hydrology (UPH) – a community perspective - Günter Blöschl; Marc F.P. Bierkens; Antonio Chambel; Christophe Cudennec; Georgia Destouni; Aldo Fiori; James W. Kirchner; Jeffrey J. McDonnell; Hubert H.G. Savenije; Murugesu Sivapalan; Christine Stumpp; Elena Toth; et al. (Hydrological Sciences Journal, 2019)

Modulation of the Expression of Immune-related Gene in Atlantic and Coho Salmon during Infestation with the Sea lice Caligus rogercresseyi - Juan Pablo Pontigo; Julia Saravia; Ricardo Oyarzún; Margarita P. González; Christopher Hawes; Francisco J. Morera; Jorge Pino; Simon Wadsworth; Jose Luis P. Muñoz; Luis Vargas-Chacoff (Fishes, 2019)
Caligus rogercresseyi, a marine ectoparasite, causes notable economic losses for the Chilean salmonid industry. Nevertheless, the immunological responses of infected fish remain poorly understood, including proinflammatory cytokine generation and the respective modulatory effects of various cytokine receptors. This study evaluated mRNA expression of the NLRC5, major histocompatibility complex (MHC) class II, I-kappa-B-alpha, a regulatory that inhibits NF-kappa-B, and proinflammatory cytokines (IL-1β and IL-18) in the liver and muscle of Atlantic salmon (Salmo salar) and Coho salmon (Oncorhynchus kisutch) during a time-course C. rogercresseyi infestation trial. All assessed mRNA were strongly regulated during infestation, but S. salar showed up-regulated expression, possibly accounting for the high infestation vulnerability of this salmonid. In conclusion, this work helps to understand the modulation of the expression of different transcripts involved over short periods of C. rogercresseyi infestation in two salmonid species (S. salar and O. kisutch).

Towards Comprehensive Observing and Modeling Systems for Monitoring and Predicting Regional to Coastal Sea Level - Rui M. Ponte; Mark Carson; Mauro Cirano; Catia M. Domingues; Svetlana Jevrejeva; Marta Marcos; Gary Mitchum; R. S. W. van de Wal; Philip L. Woodworth; Michaël Ablain; Fabrice Ardhuin; Valérie Ballu; et al. (Frontiers in Marine Science, 2019)

Causes and analytical impacts of missing data in RADseq phylogenetics: Insights from an African frog ( Afrixalus ) - Marco Crotti; Christopher D. Barratt; Simon P. Loader; David J. Gower; Jeffrey W. Streicher (Zoologica Scripta, 2019)
Restriction site‐associated DNA sequencing (RADseq) has emerged as a useful tool in systematics and population genomics. A common feature of RADseq data sets is that they contain missing data that arise from multiple sources including genealogical sampling bias, assembly methodology and sequencing error. Many RADseq studies have demonstrated that allowing sites (single nucleotide polymorphisms, SNPs) with missing data can increase support for phylogenetic hypotheses. Two non‐mutually exclusive explanations for this observation are that (a) larger data sets contain more phylogenetic information; and (b) excluding missing data disproportionally removes sites with the highest mutation rates, causing the exclusion of characters that are likely variable and informative. Using a RADseq data set derived from the East African banana frog, Afrixalus fornasini (up to 1.1 million SNPs), we found that missing data thresholds were positively correlated with the proportion of parsimony‐informative sites and mean branch support. Using three proxies for estimating site‐specific rate, we found that the most conservative missing data strategies excluded rapidly evolving sites, with four‐state sites present only when allowing ≥60% missing data per SNP. Topological similarity among estimated phylogenies was highest for the data sets with ≥60% missing data per SNP. Our results suggest that several desirable phylogenetic qualities were observed when allowing ≥60% missing data per SNP. However, at the highest missing data thresholds (80% and 90% missing data per SNP), we observed differences in performance between high‐ and mixed‐weight DNA extraction samples, which may indicate there are trade‐offs to consider when using degraded genomic template with RADseq protocols.

The paleobiogeographical significance of the Silurian and Devonian trilobites of Japan - Christopher P. Stocker; Derek J. Siveter; Philip D. Lane; Mark Williams; Tatsuo Oji; Simon R. Wallis; Gengo Tanaka; Toshifumi Komatsu; David J. Siveter; Thijs R. A. Vandenbroucke (Island Arc, 2019)
Six major groups of trilobites from the Silurian and Devonian of Japan are evaluated for their paleobiogeographical signature. Silurian illaenids and scutelluids show four generic‐level and at least two species‐level links with the Australian segment of the Gondwana paleocontinent; encrinurids also indicate two generic‐level links with Australia and also the South China paleocontinent; whilst Devonian phacopids, and possibly proetids, suggest at least two generic‐level links with the North China paleocontinent. These different patterns may reflect the fragmentary biostratigraphical record of Japanese trilobites, but they also appear to reflect paleoenvironmental parameters associated with lithofacies, and paleoecology. Thus, Japanese assemblages of proetids and phacopids occurring in deep‐water clastic lithofacies have counterparts in similar settings in North China, and Japanese scutelluids and illaenids are strongly associated with shallow marine carbonate lithofacies that are similar to those of their occurrences in Australia. Japanese encrinurids occur in carbonate rocks indicative of shallow marine settings in the Kurosegawa Terrane, and they demonstrate a consistent paleobiogeographical affinity with Australia and South China. Larval ecology cannot be directly assessed for Japanese trilobite groups. However, proetids have consistently been shown to have planktonic protaspides, whereas illaenids, scutelluids, and encrinurids have benthic protaspides. Planktonic protaspides would have a greater propensity for distribution in ocean currents than benthic ones, and therefore may be of more limited paleobiogeographical utility. The combined data from the six different groups indicates that the complex paleobiogeographical patterns of the Japanese trilobite assemblages need to be interpreted with caution, and similarity of taxa does not necessarily denote paleogeographical proximity to other regions.

Challenges and Prospects in Ocean Circulation Models - Baylor Fox-Kemper; Alistair Adcroft; Claus W. Böning; Eric P. Chassignet; Enrique Curchitser; Gokhan Danabasoglu; Carsten Eden; Matthew H. England; Rüdiger Gerdes; Richard J. Greatbatch; Stephen M. Griffies; Robert W. Hallberg; et al. (Frontiers in Marine Science, 2019)

Effects of garden management practices, by different types of gardeners, on human wellbeing and ecological and soil sustainability in Swiss cities - Robert Home; Olivia Lewis; Nicole Bauer; Andreas Fliessbach; David Frey; Stéphanie Lichtsteiner; Marco Moretti; Simon Tresch; Christopher Young; Andrea Zanetta; Matthias Stolze (Urban Ecosystems, 2019)

Development and Implementation of a Continuing Medical Education Program in Canada: Knowledge Translation for Renal Cell Carcinoma (KT4RCC) - Luke T. Lavallée; Ryan Fitzpatrick; Lori A. Wood; Joan Basiuk; Christopher Knee; Sonya Cnossen; Ranjeeta Mallick; Kelsey Witiuk; Marie Vanhuyse; Simon Tanguay; Antonio Finelli; Michael A. S. Jewett; et al. (Journal of Cancer Education, 2019)

Compositional response of Amazon forests to climate change - Adriane Esquivel‐Muelbert; Timothy R. Baker; Kyle G. Dexter; Simon L. Lewis; Roel J. W. Brienen; Ted R. Feldpausch; Jon Lloyd; Abel Monteagudo‐Mendoza; Luzmila Arroyo; Esteban Álvarez-Dávila; Niro Higuchi; Beatriz S. Marimon; et al. (Global Change Biology, 2019)
Most of the planet's diversity is concentrated in the tropics, which includes many regions undergoing rapid climate change. Yet, while climate‐induced biodiversity changes are widely documented elsewhere, few studies have addressed this issue for lowland tropical ecosystems. Here we investigate whether the floristic and functional composition of intact lowland Amazonian forests have been changing by evaluating records from 106 long‐term inventory plots spanning 30 years. We analyse three traits that have been hypothesized to respond to different environmental drivers (increase in moisture stress and atmospheric CO 2 concentrations): maximum tree size, biogeographic water‐deficit affiliation and wood density. Tree communities have become increasingly dominated by large‐statured taxa, but to date there has been no detectable change in mean wood density or water deficit affiliation at the community level, despite most forest plots having experienced an intensification of the dry season. However, among newly recruited trees, dry‐affiliated genera have become more abundant, while the mortality of wet‐affiliated genera has increased in those plots where the dry season has intensified most. Thus, a slow shift to a more dry‐affiliated Amazonia is underway, with changes in compositional dynamics (recruits and mortality) consistent with climate‐change drivers, but yet to significantly impact whole‐community composition. The Amazon observational record suggests that the increase in atmospheric CO 2 is driving a shift within tree communities to large‐statured species and that climate changes to date will impact forest composition, but long generation times of tropical trees mean that biodiversity change is lagging behind climate change.

Potential Mitigation and Restoration Actions in Ecosystems Impacted by Seabed Mining - Daphne Cuvelier; Sabine Gollner; Daniel O. B. Jones; Stefanie Kaiser; Pedro Martínez Arbizu; Lena Menzel; Nélia C. Mestre; Telmo Morato; Christopher Pham; Florence Pradillon; Autun Purser; Uwe Raschka; et al. (Frontiers in Marine Science, 2018)

Vanishing refuge? Testing the forest refuge hypothesis in coastal East Africa using genome‐wide sequence data for seven amphibians - Christopher D. Barratt; Beryl A. Bwong; Robert Jehle; H. Christoph Liedtke; Peter Nagel; Renske E. Onstein; Daniel M. Portik; Jeffrey W. Streicher; Simon P. Loader (Molecular Ecology, 2018)
High‐throughput sequencing data have greatly improved our ability to understand the processes that contribute to current biodiversity patterns. The “vanishing refuge” diversification model is speculated for the coastal forests of eastern Africa, whereby some taxa have persisted and diversified between forest refugia, while others have switched to becoming generalists also present in non‐forest habitats. Complex arrangements of geographical barriers (hydrology and topography) and ecological gradients between forest and non‐forest habitats may have further influenced the region's biodiversity, but elucidation of general diversification processes has been limited by lack of suitable data. Here, we explicitly test alternative diversification modes in the coastal forests using genome‐wide single nucleotide polymorphisms, mtDNA, spatial and environmental data for three forest ( Arthroleptis xenodactyloides , Leptopelis flavomaculatus and Afrixalus sylvaticus ) and four generalist ( Afrixalus fornasini , A. delicatus , Leptopelis concolor and Leptopelis argenteus ) amphibians. Multiple analyses provide insight about divergence times, spatial population structure, dispersal barriers, environmental stability and demographic history. We reveal highly congruent intra‐specific diversity and population structure across taxa, with most divergences occurring during the late Pliocene and Pleistocene. Although stability models support the existence of some forest refugia, dispersal barriers and demographic models point towards idiosyncratic diversification modes across taxa. We identify a consistent role for riverine barriers in the diversification of generalist taxa, but mechanisms of diversification are more complex for forest taxa and potentially include topographical barriers, forest refugia and ecological gradients. Our work demonstrates the complexity of diversification processes in this region, which vary between forest and generalist taxa, but also for ecologically similar species with shared population boundaries.

Geographic and temporal variations in turbulent heat loss from lakes: A global analysis across 45 lakes - R. Iestyn Woolway; Piet Verburg; John D. Lenters; Christopher J. Merchant; David P. Hamilton; Justin Brookes; Elvira de Eyto; Sean Kelly; Nathan C. Healey; Simon Hook; Alo Laas; Don Pierson; et al. (Limnology and Oceanography, 2018)
Heat fluxes at the lake surface play an integral part in determining the energy budget and thermal structure in lakes, including regulating how lakes respond to climate change. We explore patterns in turbulent heat fluxes, which vary across temporal and spatial scales, using in situ high‐frequency monitoring data from 45 globally distributed lakes. Our analysis demonstrates that some of the lakes studied follow a marked seasonal cycle in their turbulent surface fluxes and that turbulent heat loss is highest in larger lakes and those situated at low latitude. The Bowen ratio, which is the ratio of mean sensible to mean latent heat fluxes, is smaller at low latitudes and, in turn, the relative contribution of evaporative to total turbulent heat loss increases toward the tropics. Latent heat transfer ranged from ~ 60% to > 90% of total turbulent heat loss in the examined lakes. The Bowen ratio ranged from 0.04 to 0.69 and correlated significantly with latitude. The relative contributions to total turbulent heat loss therefore differ among lakes, and these contributions are influenced greatly by lake location. Our findings have implications for understanding the role of lakes in the climate system, effects on the lake water balance, and temperature‐dependent processes in lakes.

Recent multivariate changes in the North Atlantic climate system, with a focus on 2005–2016 - Jon Robson; Rowan T. Sutton; Alex Archibald; Fenwick Cooper; Matthew Christensen; Lesley J. Gray; N. Penny Holliday; Claire Macintosh; Malcolm McMillan; Ben Moat; Maria Russo; Rachel Tilling; et al. (International Journal of Climatology, 2018)
Major changes are occurring across the North Atlantic climate system, including in the atmosphere, ocean and cryosphere, and many observed changes are unprecedented in instrumental records. As the changes in the North Atlantic directly affect the climate and air quality of the surrounding continents, it is important to fully understand how and why the changes are taking place, not least to predict how the region will change in the future. To this end, this article characterizes the recent observed changes in the North Atlantic region, especially in the period 2005–2016, across many different aspects of the system including: atmospheric circulation; atmospheric composition; clouds and aerosols; ocean circulation and properties; and the cryosphere. Recent changes include: an increase in the speed of the North Atlantic jet stream in winter; a southward shift in the North Atlantic jet stream in summer, associated with a weakening summer North Atlantic Oscillation; increases in ozone and methane; increases in net absorbed radiation in the mid‐latitude western Atlantic, linked to an increase in the abundance of high level clouds and a reduction in low level clouds; cooling of sea surface temperatures in the North Atlantic subpolar gyre, concomitant with increases in the western subtropical gyre, and a decline in the Atlantic Ocean's overturning circulation; a decline in Atlantic sector Arctic sea ice and rapid melting of the Greenland Ice Sheet. There are many interactions between these changes, but these interactions are poorly understood. This article concludes by highlighting some of the key outstanding questions.

Selective effects of 5-HT2C receptor modulation on performance of a novel valence-probe visual discrimination task and probabilistic reversal learning in mice - Benjamin U. Phillips; Sigma Dewan; Simon R. O. Nilsson; Trevor W. Robbins; Christopher J. Heath; Lisa M. Saksida; Timothy J. Bussey; Johan Alsiö (Psychopharmacology, 2018)

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

Ocean acidification in New Zealand waters: trends and impacts - Cliff S. Law; James J. Bell; Helen C. Bostock; Chris E. Cornwall; Vonda J. Cummings; Kim Currie; Simon K. Davy; Malindi Gammon; Christopher D. Hepburn; Catriona L. Hurd; Miles Lamare; Sara E. Mikaloff‐Fletcher; et al. (New Zealand Journal of Marine and Freshwater Research, 2018)
The threat posed by ocean acidification (OA) to the diversity and productivity of New Zealand marine ecosystems is assessed in a synthesis of published trends and impacts. A 20‐year time series in Subantarctic water, and a national coastal monitoring programme, provide insight into pH variability, and context for experimental design, modelling and projections. A review of the potential impact of changes in the carbonate system on the major phyla in New Zealand waters confirms international observations that calcifying organisms, and particularly their early life‐history stages, are vulnerable. The synthesis considers ecosystem and socio‐economic impacts, and identifies current knowledge gaps and future research directions, including mechanistic studies of OA sensitivity. Advanced ecosystem models of OA, that incorporate the indirect effects of OA and interactions with other climate stressors, are required for robust projection of the future status of New Zealand marine ecosystems.

How ecology shapes exploitation: a framework to predict the behavioural response of human and animal foragers along exploration–exploitation trade‐offs - Christopher T. Monk; Matthieu Barbier; Pawel Romanczuk; James R. Watson; Josep Alós; Shinnosuke Nakayama; Daniel I. Rubenstein; Simon A. Levin; Robert Arlinghaus (Ecology Letters, 2018)
Understanding how humans and other animals behave in response to changes in their environments is vital for predicting population dynamics and the trajectory of coupled social‐ecological systems. Here, we present a novel framework for identifying emergent social behaviours in foragers (including humans engaged in fishing or hunting) in predator–prey contexts based on the exploration difficulty and exploitation potential of a renewable natural resource. A qualitative framework is introduced that predicts when foragers should behave territorially, search collectively, act independently or switch among these states. To validate it, we derived quantitative predictions from two models of different structure: a generic mathematical model, and a lattice‐based evolutionary model emphasising exploitation and exclusion costs. These models independently identified that the exploration difficulty and exploitation potential of the natural resource controls the social behaviour of resource exploiters. Our theoretical predictions were finally compared to a diverse set of empirical cases focusing on fisheries and aquatic organisms across a range of taxa, substantiating the framework's predictions. Understanding social behaviour for given social‐ecological characteristics has important implications, particularly for the design of governance structures and regulations to move exploited systems, such as fisheries, towards sustainability. Our framework provides concrete steps in this direction.

Transformation in a changing climate: a research agenda - Ioan Fazey; Peter Moug; Simon Allen; Kate Beckmann; David Blackwood; Mike Bonaventura; Kathryn Burnett; Mike Danson; Ruth Falconer; Alexandre S. Gagnon; Rachel Harkness; Anthony Hodgson; et al. (Climate and Development, 2018)

Trade‐offs in triple‐bottom‐line outcomes when recovering fisheries - Christopher J Brown; Glenn Althor; Benjamin S Halpern; Md Sayed Iftekhar; Carissa J Klein; Simon Linke; Elizabeth C Pryde; Steven Schilizzi; James E M Watson; Becky Twohey; Hugh P Possingham (Fish and Fisheries, 2018)
Almost all environmental management comes at an economic cost that may not be borne equitably by all stakeholders. Here, we investigate how heterogeneity in catch and profits among fishers influences the trade‐off among the triple‐bottom‐line objectives of recovering a fish population, maximizing its economic value and distributing restrictions equitably across fishers. As a case‐study, we examine management reform of an ecologically and economically important coral reef fishery operating within the Great Barrier Reef Marine Park. Using a simulation model, we find that total profitability of the fishing industry is 40% lower if recovery plans are equitable when compared to the most economically efficient plan. However, efficient recovery plans were typically highly inequitable because they required some fishers to cease fishing. Equity was defined according to different norms, and the efficiency loss was greatest when catch losses were shared equally across fishers rather than in proportion to their historical catch. We then varied key social, economic and biological parameters to identify cases when equity and efficient recovery would trade‐off most strongly. Recovery plans could be both efficient and equitable when heterogeneity in fisher's catches and individual catch efficiencies was lower. If fishers were homogenous then equitable plans could have maximal economic efficiency. These results emphasize the importance of considering heterogeneity in individual fishers when designing recovery plans. Recovery plans that are inequitable may often fail to gain stakeholder support, so in fisheries with high heterogeneity we should temper our expectations for marked increases in profits.

iDNA at Sea: Recovery of Whale Shark (Rhincodon typus) Mitochondrial DNA Sequences from the Whale Shark Copepod (Pandarus rhincodonicus) Confirms Global Population Structure - Mark Meekan; Christopher M. Austin; Mun H. Tan; Nu-Wei V. Wei; Adam Miller; Simon J. Pierce; David Rowat; Guy Stevens; Tim K. Davies; Alessandro Ponzo; Han Ming Gan (Frontiers in Marine Science, 2017)

Hydrological Outlook UK: an operational streamflow and groundwater level forecasting system at monthly to seasonal time scales - Christel Prudhomme; Jamie Hannaford; Shaun Harrigan; David Boorman; Jeff Knight; Victoria Bell; Christopher Jackson; Cecilia Svensson; Simon Parry; Nuria Bachiller-Jareno; Helen Davies; Richard Davis; et al. (Hydrological Sciences Journal, 2017)

The Influence of Legacy P on Lake Water Quality in a Midwestern Agricultural Watershed - Melissa Motew; Xi Chen; Eric G. Booth; Stephen R. Carpenter; Pavel Pinkas; Samuel C. Zipper; Steven P. Loheide; Simon D. Donner; Kai Tsuruta; Peter A. Vadas; Christopher J. Kucharik (Ecosystems, 2017)

Shelter use by large reef fishes: long-term occupancy and the impacts of disturbance - Joanna A. Khan; Christopher H. R. Goatley; Simon J. Brandl; Sterling B. Tebbett; David R. Bellwood (Coral Reefs, 2017)

A Wireless Pressure Sensor for Continuous Monitoring of Intraocular Pressure in Conscious Animals - Simon A. Bello; Christopher L. Passaglia (Annals of Biomedical Engineering, 2017)

Microvascular ultrastructural changes precede cognitive impairment in the murine APPswe/PS1dE9 model of Alzheimer’s disease - Patricia Kelly; Paul Denver; Simon C. Satchell; Maximilian Ackermann; Moritz A. Konerding; Christopher A. Mitchell (Angiogenesis, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Lingual tactile sensitivity: effect of age group, sex, and fungiform papillae density - Ronald G. Bangcuyo; Christopher T. Simons (Experimental Brain Research, 2017)

Lyophilization of an Adjuvanted Mycobacterium tuberculosis Vaccine in a Single-Chamber Pharmaceutical Cartridge - Lucien Barnes V; Dawn M. Fedor; Simon Williams; Quinton M. Dowling; Michelle C. Archer; Sylvain Cloutier; Sarah Parker; Thomas S. Vedvick; Christopher B. Fox; Ryan M. Kramer (AAPS PharmSciTech, 2017)

Population-based assessment of racial/ethnic differences in utilization of radical cystectomy for patients diagnosed with bladder cancer - Stephen B. Williams; Jinhai Huo; Christopher D. Kosarek; Karim Chamie; Selwyn O. Rogers; Michele A. Williams; Sharon H. Giordano; Simon P. Kim; Ashish M. Kamat (Cancer Causes & Control, 2017)

Development of a Smart Pump for Monitoring and Controlling Intraocular Pressure - Simon A. Bello; Sharad Malavade; Christopher L. Passaglia (Annals of Biomedical Engineering, 2017)

The use of donor scleral patch in ophthalmic surgery - Christopher Hodge; Gerard Sutton; Raj Devasahayam; Pierre Georges; Jane Treloggen; Simon Cooper; Con Petsoglou (Cell and Tissue Banking, 2017)

Denial of long‐term issues with agriculture on tropical peatlands will have devastating consequences - Lahiru S. Wijedasa; Jyrki Jauhiainen; Mari Könönen; Maija Lampela; Harri Vasander; Marie‐Claire Leblanc; Stephanie Evers; Thomas E. L. Smith; Catherine M. Yule; Helena Varkkey; Massimo Lupascu; Faizal Parish; et al. (Global Change Biology, 2017)

A test of trophic cascade theory: fish and benthic assemblages across a predator density gradient on coral reefs - Jordan M. Casey; Andrew H. Baird; Simon J. Brandl; Mia O. Hoogenboom; Justin R. Rizzari; Ashley J. Frisch; Christopher E. Mirbach; Sean R. Connolly (Oecologia, 2017)

Where Does River Runoff Matter for Coastal Marine Conservation? - Alexa Fredston-Hermann; Christopher J. Brown; Simon Albert; Carissa J. Klein; Sangeeta Mangubhai; Joanna L. Nelson; Lida Teneva; Amelia Wenger; Steven D. Gaines; Benjamin S. Halpern (Frontiers in Marine Science, 2016)

Expression of the zinc importer protein ZIP9/SLC39A9 in glioblastoma cells affects phosphorylation states of p53 and GSK-3β and causes increased cell migration - Nico Münnich; Simon Wernhart; Christer Hogstrand; Uwe Schlomann; Christopher Nimsky; Jörg W. Bartsch (BioMetals, 2016)

Performance on the Cogstate Brief Battery Is Related to Amyloid Levels and Hippocampal Volume in Very Mild Dementia - Yen Ying Lim; Victor L. Villemagne; Simon M. Laws; Robert H. Pietrzak; David Ames; Christopher Fowler; Stephanie Rainey-Smith; Peter J. Snyder; Pierrick Bourgeat; Ralph N. Martins; Olivier Salvado; Christopher C. Rowe; et al. (Journal of Molecular Neuroscience, 2016)

Remediation of metalliferous mines, revegetation challenges and emerging prospects in semi-arid and arid conditions - Ramkrishna Nirola; Mallavarapu Megharaj; Simon Beecham; Rupak Aryal; Palanisami Thavamani; Kadiyala Vankateswarlu; Christopher Saint (Environmental Science and Pollution Research, 2016)

Ontogenetic shifts in the social behaviour of pairing coral reef rabbitfishes (Siganidae) - Christopher E. Mirbach; Simon J. Brandl (Marine Biology Research, 2016)

Bridging the Gap between Policy and Science in Assessing the Health Status of Marine Ecosystems - Angel Borja; Michael Elliott; Paul V. R. Snelgrove; Melanie C. Austen; Torsten Berg; Sabine Cochrane; Jacob Carstensen; Roberto Danovaro; Simon Greenstreet; Anna-Stiina Heiskanen; Christopher P. Lynam; Marianna Mea; et al. (Frontiers in Marine Science, 2016)

Implementation of Organ Culture storage of donor corneas: a 3 year study of its impact on the corneal transplant wait list at the Lions New South Wales Eye Bank - Raj Devasahayam; Pierre Georges; Christopher Hodge; Jane Treloggen; Simon Cooper; Con Petsoglou; Gerard Sutton; Meidong Zhu (Cell and Tissue Banking, 2016)

A mouse model of the 15q13.3 microdeletion syndrome shows prefrontal neurophysiological dysfunctions and attentional impairment - Simon R. O. Nilsson; Pau Celada; Kim Fejgin; Jonas Thelin; Jacob Nielsen; Noemí Santana; Christopher J. Heath; Peter H. Larsen; Vibeke Nielsen; Brianne A. Kent; Lisa M. Saksida; Tine B. Stensbøl; et al. (Psychopharmacology, 2016)

Association of genetic susceptibility variants for type 2 diabetes with breast cancer risk in women of European ancestry - Zhiguo Zhao; Wanqing Wen; Kyriaki Michailidou; Manjeet K. Bolla; Qin Wang; Ben Zhang; Jirong Long; Xiao-Ou Shu; Marjanka K. Schmidt; Roger L. Milne; Montserrat García-Closas; Jenny Chang-Claude; et al. (Cancer Causes & Control, 2016)

A framework for understanding climate change impacts on coral reef social–ecological systems - Joshua Eli Cinner; Morgan Stuart Pratchett; Nicholas Anthony James Graham; Vanessa Messmer; Mariana Menezes Prata Bezerra Fuentes; Tracy Ainsworth; Natalie Ban; Line Kolind Bay; Jessica Blythe; Delphine Dissard; Simon Dunn; Louisa Evans; et al. (Regional Environmental Change, 2016)

Mineralogy and mineral chemistry of detrital heavy minerals from the Rhine River in Germany as evidence to their provenance, sedimentary and depositional history: focus on platinum-group minerals and remarks on cassiterite, columbite-group minerals and uraninite - Thomas Oberthür; Frank Melcher; Simon Goldmann; Hermann Wotruba; Axel Gerdes; Arjan Dijkstra; Christopher W. Dale (International Journal of Earth Sciences, 2016)

Contributions of a global network of tree diversity experiments to sustainable forest plantations - Kris Verheyen; Margot Vanhellemont; Harald Auge; Lander Baeten; Christopher Baraloto; Nadia Barsoum; Simon Bilodeau-Gauthier; Helge Bruelheide; Bastien Castagneyrol; Douglas Godbold; Josephine Haase; Andy Hector; et al. (Ambio, 2016)
The area of forest plantations is increasing worldwide helping to meet timber demand and protect natural forests. However, with global change, monospecific plantations are increasingly vulnerable to abiotic and biotic disturbances. As an adaption measure we need to move to plantations that are more diverse in genotypes, species, and structure, with a design underpinned by science. TreeDivNet, a global network of tree diversity experiments, responds to this need by assessing the advantages and disadvantages of mixed species plantations. The network currently consists of 18 experiments, distributed over 36 sites and five ecoregions. With plantations 1–15 years old, TreeDivNet can already provide relevant data for forest policy and management. In this paper, we highlight some early results on the carbon sequestration and pest resistance potential of more diverse plantations. Finally, suggestions are made for new, innovative experiments in understudied regions to complement the existing network.

Genetic variation in the immunosuppression pathway genes and breast cancer susceptibility: a pooled analysis of 42,510 cases and 40,577 controls from the Breast Cancer Association Consortium - Jieping Lei; Anja Rudolph; Kirsten B. Moysich; Sabine Behrens; Ellen L. Goode; Manjeet K. Bolla; Joe Dennis; Alison M. Dunning; Douglas F. Easton; Qin Wang; Javier Benitez; John L. Hopper; et al. (Human Genetics, 2016)

The mineralogy and fabric of ‘Brickearths’ in Kent, UK and their relationship to engineering behaviour - Antoni E. Milodowski; Kevin J. Northmore; Simon J. Kemp; David C. Entwisle; David A. Gunn; Peter D. Jackson; David I. Boardman; Aris Zoumpakis; Christopher D. F. Rogers; Neil Dixon; Ian Jefferson; Ian J. Smalley; et al. (Bulletin of Engineering Geology and the Environment, 2015)

Influences of extreme weather, climate and pesticide use on invertebrates in cereal fields over 42 years - Julie A. Ewald; Christopher J. Wheatley; Nicholas J. Aebischer; Stephen J. Moreby; Simon J. Duffield; Humphrey Q. P. Crick; Michael B. Morecroft (Global Change Biology, 2015)
Cereal fields are central to balancing food production and environmental health in the face of climate change. Within them, invertebrates provide key ecosystem services. Using 42 years of monitoring data collected in southern E ngland, we investigated the sensitivity and resilience of invertebrates in cereal fields to extreme weather events and examined the effect of long‐term changes in temperature, rainfall and pesticide use on invertebrate abundance. Of the 26 invertebrate groups examined, eleven proved sensitive to extreme weather events. Average abundance increased in hot/dry years and decreased in cold/wet years for A raneae, C icadellidae, adult H eteroptera, T hysanoptera, B raconidae, E nicmus and L athridiidae. The average abundance of D elphacidae, C ryptophagidae and M ycetophilidae increased in both hot/dry and cold/wet years relative to other years. The abundance of all 10 groups usually returned to their long‐term trend within a year after the extreme event. For five of them, sensitivity to cold/wet events was lowest (translating into higher abundances) at locations with a westerly aspect. Some long‐term trends in invertebrate abundance correlated with temperature and rainfall, indicating that climate change may affect them. However, pesticide use was more important in explaining the trends, suggesting that reduced pesticide use would mitigate the effects of climate change.

Phylogeography of six codistributed New Zealand cicadas and their relationship to multiple biogeographical boundaries suggest a re‐evaluation of the Taupo Line - Emily A. Ellis; David C. Marshall; Kathy B. R. Hill; Christopher L. Owen; Peter J. J. Kamp; Chris Simon (Journal of Biogeography, 2015)
Aim Comparative biogeographers question the extent to which codistributed species respond similarly to environmental change. Such responses should create similar, appropriately timed patterns of cladogenesis among codistributed taxa compared to evolutionary independence, which may limit the predictions that can be made for unstudied species. Here, we compare phylogeographical patterns across ecologically divergent, codistributed taxa in the light of New Zealand's palaeohistory. Location North Island, New Zealand. Methods Mitochondrial DNA from six codistributed cicada species ( Kikihia ochrina , K. cutora , K. laneorum , K. cauta , K. scutellaris and K. dugdalei ) was analysed using phylogenetic methods and molecular dating techniques. We analysed phylogeographical distributions using analysis of molecular variance ( AMOVA ) to determine the significance of hypothesized biogeographical boundaries for clade differentiation and spatial distribution of genetic diversity. Results Five species ( Kikihia ochrina , K. cutora , K. laneorum , K. cauta and K. scutellaris ) show various degrees of intraspecific concordance with biogeographical boundaries found in previously studied taxa – the Kauri Line, the Northland Line and the newly identified Cockayne's Line. Clade splits of forest species correlate with the Kauri Line and/or Northland Line, whereas splits of scrub/hill species correlate with Cockayne's Line. Four species ( Kikihia ochrina , K. cutora , K. laneorum and K. cauta ) diversified before the Last Glacial Maximum ( LGM , 20 ka), whereas two species ( K. scutellaris and K. dugdalei ) show only post‐ LGM diversification. Main conclusions Despite species idiosyncrasies, we see the imprint of shared palaeoclimatic/geological events. We distinguish between (1) the importance of biogeographical lines as the demarcation between older genetically diverse and newer genetically depauperate populations, and (2) the importance of lines as biogeographical boundaries between sister clades. We also stress the importance of dating clade splits to ensure consistency with explanations for the biogeographical lines in question. We suggest that the Taupo Line has been overemphasized as a biogeographical boundary, whereas the importance of the mountain axis running north‐east to south‐west (‘Cockayne's Line’) has been overlooked.

GPCR structure, function, drug discovery and crystallography: report from Academia-Industry International Conference (UK Royal Society) Chicheley Hall, 1–2 September 2014 - Alexander Heifetz; Gebhard F. X. Schertler; Roland Seifert; Christopher G. Tate; Patrick M. Sexton; Vsevolod V. Gurevich; Daniel Fourmy; Vadim Cherezov; Fiona H. Marshall; R. Ian Storer; Isabel Moraes; Irina G. Tikhonova; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Urbanization changes the composition and bioavailability of dissolved organic matter in headwater streams - Thomas B. Parr; Christopher S. Cronan; Tsutomu Ohno; Stuart E. G. Findlay; Sean M. C. Smith; Kevin S. Simon (Limnology and Oceanography, 2015)
Population growth in cities has resulted in the rapid expansion of urbanized land. Most research and management of stream ecosystems affected by urban expansion has focused on the maintenance and restoration of biotic communities rather than their basal resources. We examined the potential for urbanization to induce bottom‐up ecosystem effects by looking at its influence on dissolved organic matter (DOM) composition and bioavailability and microbial enzyme activity. We selected 113 headwater streams across a gradient of urbanization in central and southern Maine and used elemental and optical analyses, including parallel factor analysis of excitation‐emission matrices, to characterize DOM composition. Results show that fluorescent and stoichiometric DOM composition changed significantly across the rural to urban gradient. Specifically, the proportion of humic‐like allochthonous DOM decreased while that of more bioavailable autochthonous DOM increased in the more urbanized streams. In laboratory incubations, increased autochthonous DOM was associated with a doubling in the decay rate of dissolved organic carbon as well as increased activity of C‐acquiring enzymes. These results suggest that urbanization replaces upstream humic material with more local sources of DOM that turnover more rapidly and may drive bottom‐up changes in microbial communities and affect the quality and quantity of downstream DOM delivery.

Metagenetic analysis of patterns of distribution and diversity of marine meiobenthic eukaryotes - Vera G. Fonseca; Gary R. Carvalho; Ben Nichols; Christopher Quince; Harriet F. Johnson; Simon P. Neill; John D. Lambshead; W. Kelley Thomas; Deborah M. Power; Simon Creer (Global Ecology and Biogeography, 2014)
Aim Meiofaunal communities that inhabit the marine benthos offer unique opportunities to simultaneously study the macroecology of numerous phyla that exhibit different life‐history strategies. Here, we ask: (1) if the macroecology of meiobenthic communities is explained mainly by dispersal constraints or by environmental conditions; and (2) if levels of meiofaunal diversity surpass existing estimates based on morphological taxonomy. Location UK and mainland European coast. Methods Next‐generation sequencing techniques ( NGS ; R oche 454 FLX platform) using 18S nuclear small subunit ribosomal DNA ( rDNA ) gene. Pyrosequences were analysed using A mplicon N oise followed by chimera removal using P erseus . Results Rarefaction curves revealed that sampling saturation was only reached at 15% of sites, highlighting that the bulk of meiofaunal diversity is yet to be discovered. Overall, 1353 OTU s were recovered and assigned to 23 different phyla. The majority of sampled sites had c. 60–70 unique operational taxonomic units ( OTU s) per site, indicating high levels of beta diversity. The environmental parameters that best explained community structure were seawater temperature, geographical distance and sediment size, but most of the variability ( R 2 = 70%–80%) remains unexplained. Main conclusions High percentages of endemic OTU s suggest that meiobenthic community composition is partly niche‐driven, as observed in larger organisms, but also shares macroecological features of microorganisms by showing high levels of cosmopolitanism (albeit on a much smaller scale). Meiobenthic communities exhibited patterns of isolation by distance as well as associations between niche, latitude and temperature, indicating that meiobenthic communities result from a combination of niche assembly and dispersal processes. Conversely, isolation‐by‐distance patterns were not identified in the featured protists, suggesting that animals and protists adhere to radically different macroecological processes, linked to life‐history strategies.

Empirical modelling of site-specific errors in continuous GPS data - Michael Moore; Christopher Watson; Matt King; Simon McClusky; Paul Tregoning (Journal of Geodesy, 2014)

An assessment of chemical contaminants in sediments from the St. Thomas East End Reserves, St. Thomas, USVI - Anthony S. Pait; S. Ian Hartwell; Andrew L. Mason; Robert A. Warner; Christopher F. G. Jeffrey; Anne M. Hoffman; Dennis A. Apeti; Simon J. Pittman (Environmental Monitoring and Assessment, 2014)

Heather Moorland Vegetation and Air Pollution: A Comparison and Synthesis of Three National Gradient Studies - Richard J. Payne; Simon J. M. Caporn; Christopher D. Field; Jacky A. Carroll; Jill L. Edmondson; Andrea Britton; Nancy B. Dise (Water, Air, & Soil Pollution, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Bergmann's rule is maintained during a rapid range expansion in a damselfly - Christopher Hassall; Simon Keat; David J. Thompson; Phillip C. Watts (Global Change Biology, 2014)
Climate‐induced range shifts result in the movement of a sample of genotypes from source populations to new regions. The phenotypic consequences of those shifts depend upon the sample characteristics of the dispersive genotypes, which may act to either constrain or promote phenotypic divergence, and the degree to which plasticity influences the genotype–environment interaction. We sampled populations of the damselfly Erythromma viridulum from northern Europe to quantify the phenotypic (latitude–body size relationship based on seven morphological traits) and genetic (variation at microsatellite loci) patterns that occur during a range expansion itself. We find a weak spatial genetic structure that is indicative of high gene flow during a rapid range expansion. Despite the potentially homogenizing effect of high gene flow, however, there is extensive phenotypic variation among samples along the invasion route that manifests as a strong, positive correlation between latitude and body size consistent with Bergmann's rule. This positive correlation cannot be explained by variation in the length of larval development (voltinism). While the adaptive significance of latitudinal variation in body size remains obscure, geographical patterns in body size in odonates are apparently underpinned by phenotypic plasticity and this permits a response to one or more environmental correlates of latitude during a range expansion.

Linking nutrient enrichment and streamflow to macrophytes in agricultural streams - Christopher A. Mebane; Nancy S. Simon; Terry R. Maret (Hydrobiologia, 2014)

A genome-wide association study of breast cancer in women of African ancestry - Fang Chen; Gary K. Chen; Daniel O. Stram; Robert C. Millikan; Christine B. Ambrosone; Esther M. John; Leslie Bernstein; Wei Zheng; Julie R. Palmer; Jennifer J. Hu; Tim R. Rebbeck; Regina G. Ziegler; et al. (Human Genetics, 2013)

Trait-dependent declines of species following conversion of rain forest to oil palm plantations - Michael J. M. Senior; Keith C. Hamer; Simon Bottrell; David P. Edwards; Tom M. Fayle; Jennifer M. Lucey; Peter J. Mayhew; Robert Newton; Kelvin S.-H. Peh; Frederick H. Sheldon; Christopher Stewart; Alison R. Styring; et al. (Biodiversity and Conservation, 2013)

Evaluation of PRDM9 variation as a risk factor for recurrent genomic disorders and chromosomal non-disjunction - Christelle Borel; Fanny Cheung; Helen Stewart; David A. Koolen; Christopher Phillips; N. Simon Thomas; Patricia A. Jacobs; Stephan Eliez; Andrew J. Sharp (Human Genetics, 2012)

Characterisation of nine microsatellite loci in the caecilian amphibian Boulengerula uluguruensis (Gymnophiona), and their cross-species utility in three congeneric species - Christopher D. Barratt; Gavin J. Horsburgh; Deborah A. Dawson; David J. Gower; Mark Wilkinson; Simon P. Loader; Robert Jehle (Conservation Genetics Resources, 2012)

Estrogen-related genes and their contribution to racial differences in breast cancer risk - Kerryn W. Reding; Chu Chen; Kimberly Lowe; David R. Doody; Christopher S. Carlson; Christina T. Chen; John Houck; Linda K. Weiss; Polly A. Marchbanks; Leslie Bernstein; Robert Spirtas; Jill A. McDonald; et al. (Cancer Causes & Control, 2012)

Application of stable carbon isotopes for reconstructing salt‐marsh floral zones and relative sea level, New Jersey, USA - Andrew C. Kemp; Christopher H. Vane; Benjamin P. Horton; Simon E. Engelhart; Daria Nikitina (Journal of Quaternary Science, 2012)
We investigated use of δ 13 C in bulk organic sediment to define the botanical origin of samples preserved in coastal sediment as a means to reconstruct relative sea level in New Jersey, USA. Modern transects at three sites demonstrated that low and high salt‐marsh floral zones dominated by C 4 species ( Spartina alterniflora and Spartina patens ) were associated with sediment δ 13 C values between −18.9‰ and −15.8‰ and occurred from mean tide level (MTL) to mean higher high water (MHHW). Brackish transitional settings vegetated by Phragmites australis with Iva fructescens and Typha sp. (C 3 species) and freshwater upland samples (C 3 species) were characterized by bulk sediment δ 13 C values of −27.0‰ to −22.0‰ and existed above MHHW. Parallel transects at one site suggested that intra‐site variability was not discernible. The utility of δ 13 C values for reconstructing relative sea level in New Jersey is limited by an inability to differentiate between brackish sediments related to sea level and freshwater upland samples. To facilitate this distinction in a 4.4 m core, we used a multi‐proxy approach (δ 13 C values with presence or absence of agglutinated foraminifera) to recognize indicative meanings for four sample types. Sediment with δ 13 C values greater than −18.9‰ was derived from a vegetated salt‐marsh and formed between MTL and MHHW. Sediment with δ 13 C values less than −22.0‰ and containing agglutinated foraminifera formed in a brackish transitional zone between MHHW and highest astronomical tide (HAT). This is the narrowest elevational range of the four sample types and most precise sea‐level indicator. Sediment with δ 13 C values less than −22.0‰ and lacking foraminifera can only constrain the upper bound of former sea level. Samples with intermediate values (−22.0‰ to −18.9‰) formed between MTL and HAT. Using these indicative meanings and radiocarbon dates, we suggest that a transition from brackish to salt‐marsh δ 13 C values recorded in the core took approximately 350 years (from 1800 to 1450 cal. a BP). Copyright © 2011 John Wiley & Sons, Ltd.

A novel approach of homozygous haplotype sharing identifies candidate genes in autism spectrum disorder - Jillian P. Casey; Tiago Magalhaes; Judith M. Conroy; Regina Regan; Naisha Shah; Richard Anney; Denis C. Shields; Brett S. Abrahams; Joana Almeida; Elena Bacchelli; Anthony J. Bailey; Gillian Baird; et al. (Human Genetics, 2012)

Liver damage and systemic inflammatory responses are exacerbated by the genetic deletion of CD39 in total hepatic ischemia - Xiaofeng Sun; Masato Imai; Martina Nowak-Machen; Olaf Guckelberger; Keiichi Enjyoji; Yan Wu; Zain Khalpey; Pascal Berberat; Jeeva Munasinghe; Simon Christopher Robson (Purinergic Signalling, 2011)

Temporal and vertical variations of lipid biomarkers during a bottom ice diatom bloom in the Canadian Beaufort Sea: further evidence for the use of the IP25 biomarker as a proxy for spring Arctic sea ice - Thomas A. Brown; Simon T. Belt; Benoît Philippe; Christopher J. Mundy; Guillaume Massé; Michel Poulin; Michel Gosselin (Polar Biology, 2011)

Rethinking the evolution of extant sub‐Saharan African suids (Suidae, Artiodactyla) - Jaime Gongora; Rebecca E. Cuddahee; Fabrícia Ferreira do Nascimento; Christopher J. Palgrave; Stewart Lowden; Simon Y. W. Ho; Denbigh Simond; Chandramaya Siska Damayanti; Daniel James White; Wee Tek Tay; Ettore Randi; Hans Klingel; et al. (Zoologica Scripta, 2011)
Gongora, J., Cuddahee, R. E., do Nascimento, F. F., Palgrave, C. J., Lowden, S., Ho, S. Y. W., Simond, D., Damayanti, C. S., White, D. J., Tay, W. T., Randi, E., Klingel, H., Rodrigues‐Zarate, C. J., Allen, K., Moran, C. & Larson, G. (2011). Rethinking the evolution of extant sub‐Saharan African suids (Suidae, Artiodactyla). — Zoologica Scripta, 40 , 327–335. Although African suids have been of scientific interest for over two centuries, their origin, evolution, phylogeography and phylogenetic relationships remain contentious. There has been a long‐running debate concerning the evolution of pigs and hogs (Suidae), particularly regarding the phylogenetic relationships among extant Eurasian and African species of the subfamily Suinae. To investigate these issues, we analysed the mitochondrial and nuclear DNA sequences of extant genera of Suidae from Eurasia and Africa. Molecular phylogenetic analyses revealed that all extant sub‐Saharan African genera form a monophyletic clade separate from Eurasian suid genera, contradicting previous attempts to resolve the Suidae phylogeny. Two major sub‐Saharan African clades were identified, with Hylochoerus and Phacochoerus grouping together as a sister clade to Potamochoerus. In addition, we find that the ancestors of extant African suids may have evolved separately from the ancestors of modern day Sus and Porcula in Eurasia before they colonised Africa. Our results provide a revision of the intergeneric relationships within the family Suidae.

Smoking and alcohol consumption in relation to risk of triple-negative breast cancer in a cohort of postmenopausal women - Geoffrey C. Kabat; Mimi Kim; Amanda I. Phipps; Christopher I. Li; Catherine R. Messina; Jean Wactawski-Wende; Lewis Kuller; Michael S. Simon; Shagufta Yasmeen; Sylvia Wassertheil-Smoller; Thomas E. Rohan (Cancer Causes & Control, 2011)

Positive effects of ectomycorrhizal colonization on growth of seedlings of a tropical tree across a range of forest floor light conditions - Philippe Saner; Christopher Philipson; Robert C. Ong; Noreen Majalap; Simon Egli; Andy Hector (Plant and Soil, 2011)

Reply to Comment: Holocene palaeoceanographic changes in Barrow Strait, Canadian Arctic: foraminiferal evidence. T. R. Gregory, C. W. Smart, M. B. Hart, G. Massé, L. L. Vare and S. T. Belt (2010). Journal of Quaternary Science 25 : 903–910 - Thomas R. Gregory; Christopher W. Smart; Malcolm B. Hart; Guillaume Massé; Lindsay L. Vare; Simon T. Belt (Journal of Quaternary Science, 2010)

Holocene palaeoceanographic changes in Barrow Strait, Canadian Arctic: foraminiferal evidence - Thomas R. Gregory; Christopher W. Smart; Malcolm B. Hart; Guillaume Massé; Lindsay L. Vare; Simon T. Belt (Journal of Quaternary Science, 2010)
Holocene changes in the benthic and planktic foraminiferal fauna (>63 µm) from a marine sediment core (ARC‐3 Canadian Arctic Archipelago, 74° 16.050′ N, 91° 06.380′ W, water depth 347 m) show that significant environmental and palaeoceanographic variations occurred during the last 10 ka. Foraminiferal assemblages are restricted to the ca. 4.5–10 ka interval as younger samples are mostly barren of foraminifera due to intense carbonate dissolution after ca. 4.5 ka. Foraminiferal assemblages in the ca. 4.5–10 ka interval are dominated by the benthic species Islandiella helenae and Cassidulina reniforme (57% of total), with Elphidium clavatum , Cibicides lobatulus and Buccella frigida also being common in this interval. The dominance of these species indicates a seasonal sea ice regime which is consistent with the occurrence of the sea ice diatom‐derived organic geochemical biomarker IP 25 throughout the core. The abundances of C. reniforme and E. clavatum decline upcore; consistent with more frequent mixing of the Barrow Strait water column during the early Holocene. It is likely that the influence of CO 2 ‐rich Arctic surface water masses have caused an increase in bottom water corrosivity after ca. 8.5 ka, and dissolution has been further enhanced by sea ice‐related processes after ca. 6 ka, concomitant with increased IP 25 fluxes. Dissolution is strongest when IP 25 fluxes are highest, suggesting a link between the sea ice and benthic systems. Copyright © 2010 John Wiley & Sons, Ltd.

Rewarding and unrewarding aspects of deployment to Iraq and its association with psychological health in UK military personnel - Josefin Sundin; Nicola T. Fear; Lisa Hull; Norman Jones; Christopher Dandeker; Matthew Hotopf; Simon Wessely; Roberto J. Rona (International Archives of Occupational and Environmental Health, 2010)

Optimisation of contained Nicotiana tabacum cultivation for the production of recombinant protein pharmaceuticals - Richard Colgan; Christopher J. Atkinson; Matthew Paul; Sally Hassan; Pascal M. W. Drake; Amy L. Sexton; Simon Santa-Cruz; David James; Keith Hamp; Colin Gutteridge; Julian K-C. Ma (Transgenic Research, 2010)

Anthropogenic disturbance affects the structure of bacterial communities - Duane Ager; Simon Evans; Hong Li; Andrew K. Lilley; Christopher J. Van Der Gast (Environmental Microbiology, 2010)
Summary Patterns of taxa abundance distributions are the result of the combined effects of historical and biological processes and as such are central to ecology. It is accepted that a taxa abundance distribution for a given community of animals or plants following a perturbation will typically change in structure from one of high evenness to increasing dominance. Subsequently, such changes in evenness have been used as indicators of biological integrity and environmental assessment. Here, using replicated experimental treehole microcosms perturbed with different concentrations of the pollutant pentachlorophenol, we investigated whether changes in bacterial community structure would reflect the effects of anthropogenic stress in a similar manner to larger organisms. Community structure was visualized using rank–abundance plots fitted with linear regression models. The slopes of the regression models were used as a descriptive statistic of changes in evenness over time. Our findings showed that bacterial community structure reflected the impact and the recovery from an anthropogenic disturbance. In addition, the intensity of impact and the rate of recovery to pre‐perturbation structure were dose‐dependent. These properties of bacterial community structures may potentially provide a metric for environmental assessment and regulation.

Autism Overflows with Syntheses - Matthew K. Belmonte; Yoram S. Bonneh; Yael Adini; Portia E. Iversen; Natacha A. Akshoomoff; Tal Kenet; Christopher I. Moore; Helen J. Simon; John F. Houde; Michael M. Merzenich (Neuropsychology Review, 2009)

Mapping bathymetric and hydrographic features of Glover's Reef, Belize, with a REMUS autonomous underwater vehicle - Andrey Y. Shcherbina; Glen G. Gawarkiewicz; Christopher A. Linder; Simon R. Thorrold (Limnology and Oceanography, 2008)
We used an autonomous underwater vehicle (AUV) to survey bathymetry and water mass properties at Glover's Reef atoll in Belize as part of a multidisciplinary study of population connectivity of Nassau grouper ( Epinephelus striatus ). Nassau grouper populations are declining dramatically throughout its range in the Caribbean because of overfishing. In response, Marine Protected Areas have been established at several spawning aggregation (SPAG) sites. However, effectiveness of these measures is presently unclear, as the regional patterns of transport and recruitment of grouper larvae have not been measured in extensive field studies. As part of a pilot study to relate oceanographic processes with transport and recruitment of Nassau grouper larvae, we used a Remote Environmental Monitoring Unit(S) (REMUS) AUV to measure the bathymetry, stratification, current velocity, and chlorophyll a fluorescence around Glover's Reef. The portability of the REMUS system enabled comprehensive oceanographic data collection in a remote location with minimal infrastructure. Using REMUS, we were able to effectively map the bathymetry of the reef and the shelfbreak. These data were merged with historical bathymetric data to develop a new chart of the atoll margin. A distinct contrast in the width of the shelves on the eastern and western sides of the atoll was demonstrated, with the widest shelf coinciding with the SPAG site. Water mass structure in the vicinity of SPAG site was also markedly different from other locations on the reef, suggesting an offshore advective influence on eggs and early‐stage larvae released there.

Integration of Mouse Phenome Data Resources - John M. Hancock; Niels C. Adams; Vassilis Aidinis; Andrew Blake; Judith A. Blake; Molly Bogue; Steve D. M. Brown; Elissa J. Chesler; Duncan Davidson; Christopher Duran; Janan T. Eppig; Valérie Gailus-Durner; et al. (Mammalian Genome, 2008)

QTL analyses of lineage-negative mouse bone marrow cells labeled with Sca-1 and c-Kit - Mays Jawad; Clare Cole; Abigail Zanker; George Giotopoulos; Simon Fitch; Christopher J. Talbot; Mark Plumb (Mammalian Genome, 2008)

The Aquarius/SAC-D Mission: Designed to Meet the Salinity Remote-Sensing Challenge - Gary Lagerloef; F. Raul Colomb; Davide Le Vine; Frank Wentz; Simon Yueh; Christopher Ruf; Jonathan Lilly; John Gunn; Yi Chao; Annette deCharon; Gene Feldman; Calvin Swift (Oceanography, 2008)

Reliability of Estimating Stochastic Lung Tissue Heterogeneity from Pulmonary Impedance Spectra: A Forward-Inverse Modeling Study - David W. Kaczka; Christopher B. Massa; Brett A. Simon (Annals of Biomedical Engineering, 2007)

Reliability of Estimating Stochastic Lung Tissue Heterogeneity from Pulmonary Impedance Spectra: A Forward-Inverse Modeling Study - David W. Kaczka; Christopher B. Massa; Brett A. Simon (Annals of Biomedical Engineering, 2007)

Actinobacterial endophytes for improved crop performance - Christopher Franco; Philip Michelsen; Nigel Percy; Vanessa Conn; Erna Listiana; Simon Moll; Rosemary Loria; Justin Coombs (Australasian Plant Pathology, 2007)

Differential contributions of dopaminergic D1- and D2-like receptors to cognitive function in rhesus monkeys - Stefani N. Von Huben; Sophia A. Davis; Christopher C. Lay; Simon N. Katner; Rebecca D. Crean; Michael A. Taffe (Psychopharmacology, 2006)

Self-selected exercise intensity during household/garden activities and walking in 55 to 65-year-old females - Robert T. Withers; Anthony G. Brooks; Simon M. Gunn; John L. Plummer; Christopher J. Gore; John Cormack (European Journal of Applied Physiology, 2006)

Bacterial diversity is determined by volume in membrane bioreactors - Christopher J. Van Der Gast; Bruce Jefferson; Elizabeth Reid; Tim Robinson; Mark J. Bailey; Simon J. Judd; Ian P. Thompson (Environmental Microbiology, 2006)
Summary It has been proposed that established models and theories developed in classical ecology could be employed to greatly improve the optimization of wastewater treatment plants (WWTP) by placing the microbiological component onto a model‐predictive basis. In particular, this could be achieved by better understanding bacterial community assembly and development. The species–area relationship is one of the oldest biological laws and has been used to describe spatial diversity patterns in contiguous habitats and on islands. In the current study, bacterial communities in seven membrane bioreactors (MBR), of increasing size, located across the UK were sampled. A significant linear relationship between bacterial taxa richness and reactor size was observed and was similar to classical species–area relationships of larger organisms colonizing oceanic islands. Rank‐abundance plots revealed a gradient of greater evenness in community structure as MBR volume increased. Application of the Raup and Crick probability‐based similarity index indicated a strong role for dispersal in MBR colonization and community structure. Our findings demonstrate that the MBR sampled behaved like islands with respect to bacterial colonization in accordance with the theory of island biogeography. In addition this study provides further evidence that biodiversity at the bacterial level is more similar to that of animals and plants than previously postulated.

Evidence that Soil Carbon Pool Determines Susceptibility of Semi-Natural Ecosystems to Elevated Nitrogen Leaching - Christopher D. Evans; Brian Reynolds; Alan Jenkins; Rachel C. Helliwell; Christopher J. Curtis; Christine L. Goodale; Robert C. Ferrier; Bridget A. Emmett; Michael G. Pilkington; Simon J. M. Caporn; Jacky A. Carroll; David Norris; et al. (Ecosystems, 2006)

Late Quaternary upwelling off tropical NW Africa: new micropalaeontological evidence from ODP Hole 658C - Simon K. Haslett; Christopher W. Smart (Journal of Quaternary Science, 2006)
Planktonic foraminifera and radiolaria have been analysed in a Late Quaternary (40–0 ka) sediment sequence from Ocean Drilling Program (ODP) Hole 658C located under a coastal upwelling system near Cap Blanc, offshore northwest Africa, in order to document the palaeoceanographic history of the area. Temporal variations in species abundance and faunal assemblage analysis reveal a tripartite phased sequence of palaeoceanographic change through the Late Quaternary. Phase 1 spans 40–14.5 ka and is characterised by moderate upwelling, but Heinrich event 2 is distinguished as a brief episode of strengthened upwelling. Phase 2 begins with a change in a number of variables at ca. 14.5 ka and extends to ca. 5.5 ka. This phase is characterised by a general strengthening of upwelling, but may be subdivided into three minor phases including (a) the recognition of the Younger Dryas, marked by a temporary reduction in upwelling strength, followed by (b) an intensification of upwelling, and (c) upwelling and high productivity between 8 and 5.5 ka. This phase of upwelling corresponds with maximum Holocene cooling, possibly triggered by the collapse of the Laurentide ice sheet. Phase 3 extends from 5.5 to 0 ka and is characterised by weak upwelling and significant calcite dissolution. These phases are related to climatic events, particularly the African Humid Period (AHP), which is coincident with Phase 2. The AHP is characterised by increased precipitation, linked to an intensification of the African monsoon that enhances North East Trade Wind‐driven coastal upwelling and is associated with the expansion of continental vegetation across North Africa. Copyright © 2006 John Wiley & Sons, Ltd.

Global assessment of coral bleaching and required rates of adaptation under climate change - SIMON D. DONNER; WILLIAM J. SKIRVING; CHRISTOPHER M. LITTLE; MICHAEL OPPENHEIMER; OVE HOEGH‐GULDBERG (Global Change Biology, 2005)
Elevated ocean temperatures can cause coral bleaching, the loss of colour from reef‐building corals because of a breakdown of the symbiosis with the dinoflagellate Symbiodinium . Recent studies have warned that global climate change could increase the frequency of coral bleaching and threaten the long‐term viability of coral reefs. These assertions are based on projecting the coarse output from atmosphere–ocean general circulation models (GCMs) to the local conditions around representative coral reefs. Here, we conduct the first comprehensive global assessment of coral bleaching under climate change by adapting the NOAA Coral Reef Watch bleaching prediction method to the output of a low‐ and high‐climate sensitivity GCM. First, we develop and test algorithms for predicting mass coral bleaching with GCM‐resolution sea surface temperatures for thousands of coral reefs, using a global coral reef map and 1985–2002 bleaching prediction data. We then use the algorithms to determine the frequency of coral bleaching and required thermal adaptation by corals and their endosymbionts under two different emissions scenarios. The results indicate that bleaching could become an annual or biannual event for the vast majority of the world's coral reefs in the next 30–50 years without an increase in thermal tolerance of 0.2–1.0°C per decade. The geographic variability in required thermal adaptation found in each model and emissions scenario suggests that coral reefs in some regions, like Micronesia and western Polynesia, may be particularly vulnerable to climate change. Advances in modelling and monitoring will refine the forecast for individual reefs, but this assessment concludes that the global prognosis is unlikely to change without an accelerated effort to stabilize atmospheric greenhouse gas concentrations.

Species Review of Amphibian Extinction Risks in Madagascar: Conclusions from the Global Amphibian Assessment - FRANCO ANDREONE; JOHN E. CADLE; NEIL COX; FRANK GLAW; RONALD A. NUSSBAUM; CHRISTOPHER J. RAXWORTHY; SIMON N. STUART; DENIS VALLAN; MIGUEL VENCES (Conservation Biology, 2005)
We assessed the extinction risks of Malagasy amphibians by evaluating their distribution, occurrence in protected areas, population trends, habitat quality, and prevalence in commercial trade. We estimated and mapped the distribution of each of the 220 described Malagasy species and applied, for the first time, the IUCN Red List categories and criteria to all species described at the time of the assessment. Nine species were categorized as critically endangered, 21 as endangered, and 25 as vulnerable. The most threatened species occur on the High Plateau and/or have been subjected to overcollection for the pet trade, but restricted extent of occurrence and ongoing habitat destruction were identified as the most important factors influencing extinction threats. The two areas with the majority of threatened species were the northern Tsaratanana‐Marojejy‐Masoala highlands and the southeastern Anosy Mountains. The current system of protected areas includes 82% of the threatened amphibian species. Of the critically endangered species, 6 did not occur in any protected area. For conservation of these species we recommend the creation of a reserve for the species of the Mantella aurantiaca group, the inclusion of two Scaphiophryne species in the Convention on the International Trade in Endangered Species Appendix II, and the suspension of commercial collecting for Mantella cowani. Field surveys during the last 15 years reveal no pervasive extinction of Malagasy amphibians resulting from disease or other agents, as has been reported in some other areas of the world.

Effects of sumatriptan and eletriptan on diseased epicardial coronary arteries - Christopher M. H. Newman; Ian Starkey; Nigel Buller; Ricardo Seabra-Gomes; Simon Kirby; Jayasena Hettiarachchi; David Cumberland; William S. Hillis (European Journal of Clinical Pharmacology, 2005)

Identifying nineteenth century genealogical links from genotypes - Jim Stankovich; Melanie Bahlo; Justin P. Rubio; Christopher R. Wilkinson; Russell Thomson; Annette Banks; Maree Ring; Simon J. Foote; Terence P. Speed (Human Genetics, 2005)

The energy cost of household and garden activities in 55- to 65-year-old males - Simon M. Gunn; Anthony G. Brooks; Robert T. Withers; Christopher J. Gore; John L. Plummer; John Cormack (European Journal of Applied Physiology, 2005)

Phytoplankton growth and stoichiometry under multiple nutrient limitation - Christopher A. Klausmeier; Elena Litchman; Simon A. Levin (Limnology and Oceanography, 2004)
Phytoplankton growth and stoichiometry depend on the availability of multiple nutrients. We use a mathematical model of phytoplankton with flexible stoichiometry to explain patterns of phytoplankton composition in chemostat experiments and nutrient drawdown dynamics that are found in the field. Exponential growth and equilibrium represent two distinct phases, each amenable to mathematical analysis. In a chemostat at a fixed dilution (growth) rate, phytoplankton stoichiometry matches the nutrient supply stoichiometry over a wide range at low growth rates and over a narrow range at high growth rates. In a chemostat with a fixed nutrient supply stoichiometry, phytoplankton stoichiometry varies with dilution rate nonlinearly, between the supply stoichiometry at low dilution rates and a species‐specific optimal ratio at high dilution rates. The flexible‐stoichiometry model we study predicts low equilibrium concentrations of two nutrients over a wide range of supply ratios, contrary to the predictions of a traditional fixed‐stoichiometry model. The model is in quantitative agreement with experimental data, except at extreme nutrient supply ratios, which require a negative feedback from quota to uptake to fit the data. Our analysis points to the importance of better understanding the regulation of uptake rates in determining phytoplankton stoichiometry and incorporating this knowledge into phytoplankton models.

Effects of halothane, isoflurane, sevoflurane and desflurane on contraction of ventricular myocytes from streptozotocin-induced diabetic rats - Mark Graham; Anwar Qureshi; Rabiah Noueihed; Simon Harrison; Frank Christopher Howarth (Molecular and Cellular Biochemistry, 2004)

Measurement and prediction of energy expenditure in males during household and garden tasks - Simon M. Gunn; Grant E. van der Ploeg; Robert T. Withers; Christopher J. Gore; Neville Owen; Adrian E. Bauman; John Cormack (European Journal of Applied Physiology, 2004)

Measurement and prediction of energy expenditure in males during household and garden tasks - Simon M. Gunn; Grant E. van der Ploeg; Robert T. Withers; Christopher J. Gore; Neville Owen; Adrian E. Bauman; John Cormack (European Journal of Applied Physiology, 2004)

Geochemistry and Isotopic Composition of H2S-rich Water in Flooded Underground Mine Workings, Butte, Montana, USA - Christopher H. Gammons; Simon R. Poulson; John J. Metesh; Terence E. Duaime; Amber R. Henne (Mine Water and the Environment, 2003)

The effect of modified atmospheres on the survival of the eggs of four storage mite species - Simon T. Conyers; Christopher H. Bell (Experimental and Applied Acarology, 2003)

Anthocyanic vacuolar inclusions (AVIs) selectively bind acylated anthocyanins in Vitis vinifera L. (grapevine) suspension culture - Simon Conn; Wei Zhang; Christopher Franco (Biotechnology Letters, 2003)

Extinction times for closed epidemics: the effects of host spatial structure - Andrew W. Park; Simon Gubbins; Christopher A. Gilligan (Ecology Letters, 2002)
Although of practical importance, the relationship between the duration of an epidemic and host spatial structure is poorly understood. Here we use a stochastic metapopulation model for the transmission of infection in a spatially structured host population. There are three qualitatively different regimes for the extinction time, which depend on patch population size, the within‐patch basic reproductive number and the strength of coupling between patches. In the first regime, the extinction time for the metapopulation (i.e. from all patches) is approximately equal to the extinction time for a single patch. In the second regime, the metapopulation extinction time is maximal but also highly variable. In the third regime, the extinction time for the metapopulation ( T E ) is given by T E = a + bn 1/2 where a is the local extinction time (i.e. from last patch), b is the transit time (i.e. the time taken for infection to spread from one patch to another) and n is the total number of patches.

c-fos induction in rat superficial dorsal horn following cutaneous application of noxious chemical or mechanical stimuli - Steven L. Jinks; Christopher T. Simons; Jean-Marc Dessirier; Mirela Iodi Carstens; Joseph F. Antognini; E. Carstens (Experimental Brain Research, 2002)

Expression patterns of cell wall-modifying enzymes during grape berry development - Kylie J. Nunan; Christopher Davies; Simon P. Robinson; Geoffrey B. Fincher (Planta, 2001)

Analgesia induced by chronic nicotine infusion in rats - Carstens E.; Kenton Anderson; Christopher Simons; Mirela Carstens; Steven Jinks (Psychopharmacology, 2001)

Allochronic speciation, secondary contact, and reproductive character displacement in periodical cicadas (Hemiptera: Magicicada spp.): genetic, morphological, and behavioural evidence - John R. Cooley; Chris Simon; David C. Marshall; Karen Slon; Christopher Ehrhardt (Molecular Ecology, 2001)
Periodical cicadas have proven useful in testing a variety of ecological and evolutionary hypotheses because of their unusual life history, extraordinary abundance, and wide geographical range. Periodical cicadas provide the best examples of synchronous periodicity and predator satiation in the animal kingdom, and are excellent illustrations of habitat partitioning (by the three morphologically distinct species groups), incipient species (the year classes or broods), and cryptic species (a newly discovered 13‐year species, Magicicada neotredecim ). They are particularly useful for exploring questions regarding speciation via temporal isolation, or allochronic speciation. Recently, data were presented that provided strong support for an instance of allochronic speciation by life‐cycle switching. This speciation event resulted in the formation of a new 13‐year species from a 17‐year species and led to secondary contact between two formerly separated lineages, one represented by the new 13‐year cicadas (and their 17‐year ancestors), and the other represented by the pre‐existing 13‐year cicadas. Allozyme frequency data, mitochondrial DNA (mtDNA), and abdominal colour were shown to be correlated genetic markers supporting the life‐cycle switching/allochronic speciation hypothesis. In addition, a striking pattern of reproductive character displacement in male call pitch and female pitch preference between the two 13‐year species was discovered. In this paper we report a strong association between calling song pitch and mtDNA haplotype for 101 individuals from a single locality within the M. tredecim/M. neotredecim contact zone and a strong association between abdomen colour and mtDNA haplotype. We conclude by reviewing proposed mechanisms for allochronic speciation and reproductive character displacement.

Role of neuronal nicotinic-acetylcholine receptors in the activation of neurons in trigeminal subnucleus caudalis by nicotine delivered to the oral mucosa - E. Carstens; Christopher T. Simons; Jean-Marc Dessirier; M. Iodi Carstens; Steven L. Jinks (Experimental Brain Research, 2000)

Electron spin resonance spectroscopic detection of oxygen-centred radicals in human serum following exhaustive exercise - Tony Ashton; Christopher C. Rowlands; Eleri Jones; Ian S. Young; Simon K. Jackson; Bruce Davies; John R. Peters (European Journal of Applied Physiology, 1998)